Coating composition
By combining polyazidine compounds and carboxylic acid functional polymers in aqueous coatings, a self-crosslinked aqueous coating composition was developed, solving the complexity of mixing coating systems and the stability of crosslinking agents in the prior art. The problem has achieved the effect of efficient crosslinking and long storage life.
Patent Information
- Application Number
- CN202180010686.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-24
- Filing Date
- 2021-01-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-01-21
AI Technical Summary
The existing water-based coating systems require mixing crosslinking agents and adhesives before application, resulting in increased workload and cost, and there are also problems with the stability and safety of crosslinking agents.
开发了一种包含多氮丙啶化合物和羧酸官能聚合物的水性涂料组合物,该组合物在pH范围为8至14的条件下自交联,实现了良好的交联效率和长储存寿命。
The aqueous coating composition is capable of efficient crosslinking at room temperature, providing a one-pot solution for easy storage, disposal and coating, reducing the handling complexity of hazardous materials and improving the stability and performance of the coating.
Smart Images

Figure CN115210281B_ABST
Abstract
Description
[0001] The present invention relates to an aqueous coating composition comprising a carboxylic acid functional polymer in an aqueous medium and further comprising a polyaziridine compound. The present invention also relates to the use of such a coating composition as a one-pack coating system.
[0002] Coatings provide protection, aesthetic qualities and new functionality for various substrates with great industrial and household relevance. In this case, there is a growing demand for coatings with improved resistance (such as stain resistance and solvent resistance), improved mechanical properties and improved adhesion strength. One or more of these characteristics can be enhanced by means of crosslinking. Many crosslinking mechanisms of polymeric binders have been studied for many years, and for aqueous latex polymer dispersions, the most useful polymeric binders include isocyanate crosslinking of hydroxyl-functional polymers, carbodiimide crosslinking of carboxylic acid-functional polymers, melamine crosslinking, epoxy crosslinking and aziridine crosslinking of carboxylic acid-functional polymers.
[0003] Waterborne binders are often colloidally stabilized by carboxylic acid groups, and coating properties can be improved by using carbodiimide or aziridine crosslinkers, as the crosslinkers react with the carboxylic acid moieties of the polymer to produce a crosslinked network. Of the state-of-the-art crosslinkers described above, aziridine crosslinkers are the most versatile (most general) for room temperature curing of carboxylic acid functional polymers.
[0004] Conventional crosslinking methods generally involve the use of low molecular weight reactive organic molecules to achieve high crosslink density. Upon addition to the aqueous adhesive, these reactive molecules are generally shown to react immediately with the carboxylate functional adhesive, as well as to react with, for example, water, resulting in a limited application window for the coating composition. Therefore, these so-called 2K coating systems require the user to mix the crosslinker and adhesive just before coating, thereby incurring additional workload and cost. It would therefore be beneficial to deliver an aqueous 1K coating system with good crosslinking efficiency and long shelf life, comprising an adhesive to be crosslinked and a crosslinker.
[0005] Polyaziridine crosslinkers are the most versatile for room temperature curing of carboxylic acid functional polymers. However, the most advanced polyaziridine crosslinkers (such as those described in US-A-5133997) currently lack stability when combined with these polymers. For example, CX-100 (trimethylolpropane tris (2-methyl-1-aziridine propionate; CAS No. 64265-57-2) and XAMA-7 (pentaerythritol tris [3- (1-aziridine) propionate; CAS No. 57116-45-7) are not suitable for use in 1K systems because their uniform distribution throughout the resin matrix makes them sensitive to nucleophilic substances (such as water or carboxylate substances). In addition, these crosslinkers are hazardous materials, thereby excluding their use outside professional and controlled environments. In addition, these polyaziridines have unfavorable genotoxic characteristics.
[0006] State-of-the-art 1K systems (e.g., using keto-amine or silane condensation chemistries) offer lower performance due to reduced reactivity. In addition, these crosslinking methodologies require incorporation of specific functional monomers into the polymer backbone, increasing cost and reducing compositional freedom. For many existing 1K systems, an increase in temperature or other external trigger is required to initiate curing after film coating, further adding practical complexity. Self-crosslinkable coating compositions are crosslinkable without the need to mix reactive materials that react with groups on the crosslinkable polymer just prior to coating, although such external triggers can still be used if desired.
[0007] The object of the present invention is to provide an aqueous coating composition comprising a polyaziridine compound and a carboxylic acid functional polymer having good crosslinking efficiency and a long storage life.
[0008] Surprisingly, this object has been achieved by an aqueous dispersion having a pH in the range of 8 to 14, wherein the aqueous dispersion comprises dispersed particles of a polyaziridine compound X and dispersed particles of a carboxylic acid-functional polymer Y, and
[0009] The polyaziridine compound has:
[0010] a) 2 to 6 of the following structural units A:
[0011]
[0012] in
[0013] R1 is H,
[0014] R2 and R4 are independently selected from H or an aliphatic hydrocarbon group containing 1 to 4 carbon atoms,
[0015] R3 is an aliphatic hydrocarbon group containing 1 to 4 carbon atoms,
[0016] m is an integer from 1 to 6,
[0017] R' and R" are according to (1) or (2):
[0018] (1) R'=H or an aliphatic hydrocarbon group containing 1 to 14 carbon atoms; and R"=H, an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, an alicyclic hydrocarbon group containing 5 to 12 carbon atoms, an aromatic hydrocarbon group containing 6 to 12 carbon atoms, CH2-O-(C=O)-R"', CH2-OR"" or CH2-(OCR""'HCR""'H) n -OR""", wherein R"' is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms and R"" is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms or an aromatic hydrocarbon group containing 6 to 12 carbon atoms, n is 1 to 35, R""' is independently H or an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, and R""" is an aliphatic hydrocarbon group containing 1 to 4 carbon atoms,
[0019] (2) R' and R" together form a saturated alicyclic hydrocarbon group containing 5 to 8 carbon atoms,
[0020] t is an integer from 0 to 3,
[0021] R5 is H or CH3,
[0022] X and Y are according to (I), (II) or (III):
[0023] (I) X and Y are both N-R6;
[0024] (II) X is O and Y is N-R6;
[0025] (III) X is N-R6 and Y is O,
[0026] wherein R6 is H or a straight or branched hydrocarbon group containing 1 to 4 carbon atoms;
[0027] b) one or more link chains, wherein each of the link chains links two of the structural units A; and
[0028] c) A molecular weight in the range of 500 Daltons to 10,000 Daltons.
[0029] It has been surprisingly found that the aqueous coating composition of the present invention has extended storage stability while also showing good crosslinking efficiency when the aqueous coating composition is dried. The composition according to the present invention exhibits an efficient crosslinking reaction at room temperature. The composition of the present invention is also easy to use, thereby providing a one-pot solution that is convenient for storage, handling and coating.
[0030] Thus, the aqueous coating composition according to the present invention can provide a self-crosslinkable composition that can be applied as a one-pack coating system without the need to mix reactive materials just prior to coating as in a two-pack coating system. The stability of the coating composition of the present invention and the improved properties of the corresponding dry film, combined with the favorable hazardous properties, result in a high performance 1K system. Such a 1K system, in which crosslinking is only triggered when the coating is applied, is very easy to use for a range of coating applicators because it reduces the handling of hazardous materials and provides good coating properties.
[0031] US-A-3523750 describes a method for modifying protein substrates such as wool with polyaziridine compounds. US-A-5258481 describes a multifunctional water-dispersible crosslinking agent, which is an oligomeric material containing a carbodiimide functional group and a reactive functional group different from the carbodiimide functional group. US-A-5241001 discloses a polyaziridine compound obtained by reacting 1-(2-hydroxyethyl)-ethyleneimine with a polyisocyanate.
[0032] For all upper and / or lower boundaries of any range given herein, unless otherwise specifically indicated, the boundary values are included in the given range. Thus, when it is said from x to y, it is meant to include x and y and also all intermediate values.
[0033] In this specification, the term "coating composition" covers paints, coatings, varnishes, adhesives and ink compositions, but is not limited to this list. The term "aliphatic hydrocarbon group" refers to alkyl, alkenyl and alkynyl groups that are optionally (herein "optionally") branched. The term "alicyclic hydrocarbon group" refers to cycloalkyl and cycloalkenyl groups that are optionally substituted by at least one aliphatic hydrocarbon group. The term "aromatic hydrocarbon group" refers to a benzene ring that is optionally substituted by at least one aliphatic hydrocarbon group. These optional aliphatic hydrocarbon substituents are preferably alkyl groups. Examples of alicyclic hydrocarbon groups with 7 carbon atoms are cycloheptyl and methyl-substituted cyclohexyl. Examples of aromatic hydrocarbon groups with 7 carbon atoms are methyl-substituted phenyl. Examples of aromatic hydrocarbon groups with 8 carbon atoms are xylyl and ethyl-substituted phenyl.
[0034] The aziridine group has the following structural formula:
[0035]
[0036] Polyaziridine compounds
[0037] R1 is H. R2 and R4 are independently selected from H or an aliphatic hydrocarbon group containing 1 to 4 carbon atoms. Preferably, R2 and R4 are independently selected from H or an aliphatic hydrocarbon group containing 1 to 2 carbon atoms.
[0038] R3 is an aliphatic hydrocarbon group having 1 to 4 carbon atoms, preferably an aliphatic hydrocarbon group having 1 to 2 carbon atoms.
[0039] In a preferred embodiment of the present invention, R2 is H, R3 is an aliphatic hydrocarbon group containing 1 to 2 carbon atoms, and R4 is H.
[0040] In a more preferred embodiment of the present invention, R2 is H, R3 is C2H5, and R4 is H. In another embodiment of the present invention, R2 is H, R3 is CH3, and R4 is H or CH3. In another even more preferred embodiment of the present invention, R2 is H, R3 is CH3, and R4 is H.
[0041] Although the structural units A present in the polyaziridine compound may independently have different R', R", R1, R2, R4, R5, X, Y, t and / or m, the structural units A present in the polyaziridine compound are preferably the same as each other.
[0042] m is an integer of 1 to 6, preferably m is 1 to 4, more preferably m is 1 or 2, and most preferably m is 1.
[0043] t is an integer of 0 to 3, and more preferably t is 0 or 1.
[0044] Preferably, R' and R" are according to (1) or (2):
[0045] (1) R'=H or an alkyl group containing 1 to 2 carbon atoms;
[0046] R"=H, an aliphatic hydrocarbon group containing 1 to 4 carbon atoms, CH2-O-(C=O)-R"', or CH2-OR"", wherein R"' is an alkyl group containing 1 to 14 carbon atoms, and R"" is an alkyl group containing 1 to 14 carbon atoms, n is 1 to 35, R""' is independently H or methyl, and R""" is an alkyl group containing 1 to 4 carbon atoms;
[0047] (2) R' and R" together form a saturated alicyclic hydrocarbon group containing 5 to 8 carbon atoms.
[0048] In a preferred embodiment of the present invention, R2 is H, R3 is an aliphatic hydrocarbon group containing 1 to 2 carbon atoms, R4 is H, m is 1, t is 0, X is O, Y is NH, R' is H, and R" is H, an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, an alicyclic hydrocarbon group containing 5 to 12 carbon atoms, an aromatic hydrocarbon group containing 6 to 12 carbon atoms, CH2-O-(C=O)-R"' or CH2-OR"", wherein R"' is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, preferably R"' is an aliphatic hydrocarbon group containing 3 to 12 carbon atoms, and R"" is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms. More preferably, R' is H and R" is an alkyl group containing 1 to 4 carbon atoms, CH2-O-(C=O)-R"', CH2-OR"", wherein R"' is an alkyl group containing 3 to 12 carbon atoms, such as neopentyl or neodecyl. Most preferably, R"' is a branched C9 alkyl group. R"" is preferably an alkyl group containing 1 to 14 carbon atoms, more preferably 1 to 12 carbon atoms. Non-limiting examples of R"" are ethyl, butyl and 2-ethylhexyl.
[0049] R5 is H or CH3.
[0050] R6 is H or a straight chain or branched hydrocarbon group containing 1 to 4 carbon atoms, preferably R6 is H
[0051] The polyaziridine compound preferably has 2 to 6 of the following structural units D:
[0052]
[0053] wherein R1, R2, R3, R4, R', R", and m and their preferences are as defined above.
[0054] Therefore, the structural unit A present in the polyaziridine compound is preferably according to structural formula D.
[0055] The polyaziridine compound contains 2 to 6 structural units A, preferably 2 to 4 structural units A, and more preferably 2 or 3 structural units A.
[0056] Polyaziridine compounds include one or more chain links, wherein each chain link chain in these chain links two structural units A in structural unit A. The chain link chain present in polyaziridine compounds is preferably composed of 4 to 300 atoms, more preferably 5 to 250 atoms, and most preferably 6 to 100 atoms. The atom of chain link is preferably C and optional N, O, S and / or P, preferably C and optional N and / or O. The chain link chain present in the polyaziridine compounds is preferably composed of 4 to 300 atoms, more preferably 5 to 250 atoms, more preferably 6 to 100 atoms, and most preferably 6 to 20 atoms. Chain link is preferably a set of covalently attached atoms, and the set of atoms is composed of i) carbon atoms, ii) carbon and nitrogen atoms or iii) carbon, oxygen and nitrogen atoms.
[0057] A linking chain is defined as the shortest chain of consecutive atoms linking two building blocks A. The figure below shows an example of a polyaziridine compound and a linking chain between two building blocks A.
[0058]
[0059] Any two structural units A present in the polyaziridine compound are linked by a linking chain as defined herein. Therefore, each structural unit A present in the polyaziridine compound is linked to each other structural unit A by a linking chain as defined herein. In the case where the polyaziridine compound has two structural units A, the polyaziridine compound has one such linking chain linking the two structural units.
[0060] In the case where the polyaziridine compound has three structural units A, the polyaziridine compound has three link chains, wherein each of the three link chains links the structural unit A with another structural unit A, that is, the first structural unit A is linked to the second structural unit A through the link chain, and the first and second structural units A are both independently linked to the third structural unit A through their corresponding link chains.
[0061] The following figures show examples of polyaziridine compounds having three structural units A, three linking chains, wherein each of the three linking chains links two structural units A.
[0062]
[0063] Polyaziridine compounds having more than two structural units A have the number of linked chains according to the following equation:
[0064] LC = {(AN-1) x AN)} / 2, where LC = the number of linking chains in the polyaziridine compound, and AN = the number of structural units A in the polyaziridine compound. Thus, for example, if there are 5 structural units A in the polyaziridine compound, AN = 5; this means that there are {(5-1) x 5} / 2 = 10 linking chains.
[0065] The molecular weight of polyaziridine compounds is preferably 600 daltons to 5000 daltons. The molecular weight of polyaziridine compounds is preferably 3800 daltons at the most, more preferably 3600 daltons at the most, more preferably 3000 daltons at the most, more preferably 1600 daltons at the most, even more preferably 1400 daltons at the most. The molecular weight of polyaziridine compounds is preferably at least 700 daltons, more preferably at least 800 daltons, even more preferably at least 840 daltons, and most preferably at least 1000 daltons. As used herein, the molecular weight of polyaziridine compounds is a calculated molecular weight. The calculated molecular weight is obtained by adding the atomic masses of all atoms present in the structural formula of polyaziridine compounds. If polyaziridine compounds are present in a composition comprising more than one polyaziridine compound according to the present invention, for example, when one or more starting materials in the starting materials for preparing polyaziridine compounds are a mixture, then molecular weight calculations can be performed for each compound present alone in the composition. As described in the experimental section below, the molecular weight of the polyaziridine compounds according to the invention can be measured using MALDI-TOF mass spectrometry.
[0066] The polyaziridine compound preferably comprises one or more linking groups, wherein each of these linking groups links two structural units A in the structural unit A, and wherein each of these linking groups consists of at least one functional group selected from the group consisting of: an aliphatic hydrocarbon functional group (preferably containing 1 to 8 carbon atoms), an alicyclic hydrocarbon functional group (preferably containing 4 to 10 carbon atoms), an aromatic hydrocarbon functional group (preferably containing 6 to 12 carbon atoms), an isocyanurate functional group, an iminooxadiazindione functional group, an ether functional group, an ester functional group, an amide functional group, a carbonate functional group, a carbamate functional group, a urea functional group, a biuret functional group, an allophanate functional group, a uretdione functional group, and any combination thereof. More preferably, the linking group is an array of continuous functional groups, wherein each functional group is selected from the group consisting of: an aliphatic hydrocarbon functional group (preferably containing 1 to 8 carbon atoms), an alicyclic hydrocarbon functional group (preferably containing 4 to 10 carbon atoms), an aromatic hydrocarbon functional group (preferably containing 6 to 12 carbon atoms), an isocyanurate functional group, an iminooxadiazinedione functional group, an ether functional group, an ester functional group, an amide functional group, a carbonate functional group, a carbamate functional group, a urea functional group, a biuret functional group, an allophanate functional group, and a uretdione functional group.
[0067] The term "aliphatic hydrocarbon functionality" refers to optionally branched alkyl, alkenyl and alkynyl groups. Although optional branches of C atoms are part of the linking group, they are not part of the linking chain.
[0068] The term "alicyclic hydrocarbon functional group" refers to cycloalkyl and cycloalkenyl groups optionally substituted with at least one aliphatic hydrocarbon group. Although the optional aliphatic hydrocarbon substituents are part of the linking group, they are not part of the linking chain. The optional aliphatic hydrocarbon substituents are preferably alkyl groups.
[0069] The term "aromatic hydrocarbon functional group" refers to a benzene ring optionally substituted with at least one aliphatic hydrocarbon group. Although the optional aliphatic hydrocarbon substituents are part of the linking group, they are not part of the linking chain. The optional aliphatic hydrocarbon substituents are preferably alkyl groups.
[0070] The isocyanurate functional group is defined as
[0071] The iminooxadiazinedione functional group is defined as
[0072] The biuret functional group is defined as
[0073] The allophanate functional group is defined as
[0074] The uretdione functional group is defined as
[0075] The following figure shows in bold the linking group of an example of a polyaziridine compound as defined herein. In this example, the linking group connecting two building blocks A in a building block A consists of the following array of consecutive functional groups: aliphatic hydrocarbon functional group 1 (straight chain C6H 12 ), isocyanurate 2 (cyclic C3N3O3) functional group and aliphatic hydrocarbon functional group 3 (straight chain C6H 12 ).
[0076]
[0077] The following figure shows in bold the following example linking groups of the polyaziridine compound as defined herein. In this example, the linking group connecting the two structural units A consists of the following array of consecutive functional groups: aliphatic hydrocarbon functional group 1 (straight chain C6H 12 ), isocyanurate 2 (cyclic C3N3O3) and aliphatic hydrocarbon functional group 3 (linear C6H 12 ).
[0078]
[0079] Any two structural units A in the structural unit A present in the polyaziridine compound as defined herein are preferably connected by a linking group, and the linking group is as defined herein. Therefore, each structural unit A present in the polyaziridine compound is preferably connected with each other structural unit A using a linking group, and the linking group is as defined in the present invention. In the case where the polyaziridine compound has two structural units A, the polyaziridine compound has such a linking group connecting the two structural units. In the case where the polyaziridine compound has three structural units A, the polyaziridine compound has three such linking groups, and each linking group in the three linking groups connects structural unit A with another structural unit A together.
[0080] The figure below shows an example of a polyaziridine compound having three structural units A, three linking groups, wherein each of the three linking groups connects two structural units A. One linking group consists of the following array of consecutive functional groups: an aliphatic hydrocarbon functional group 1 (straight-chain C6H 12 ), isocyanurate 2 (cyclic C3N3O3) and aliphatic hydrocarbon functional group 3 (linear C6H 12 For the connection between the structural units A labeled A1 and A3, the linking group consists of the following array of consecutive functional groups: aliphatic hydrocarbon functional group 1 (straight chain C6H 12), isocyanurate 2 (cyclic C3N3O3) and aliphatic hydrocarbon functional group 4 (linear C6H 12 ), while for the connection between the structural units A labeled A2 and A3, the linking group consists of the following array of consecutive functional groups: aliphatic hydrocarbon functional group 3 (straight chain C6H 12 ), isocyanurate 2 (cyclic C3N3O3) and aliphatic hydrocarbon functional group 4 (linear C6H 12 ).
[0081]
[0082]
[0083] Preferably, the linking group is composed of at least one functional group selected from the group consisting of: aliphatic hydrocarbon functional group (preferably containing 1 to 8 carbon atoms), alicyclic hydrocarbon functional group (preferably containing 4 to 10 carbon atoms), aromatic hydrocarbon functional group (preferably containing 6 to 12 carbon atoms), isocyanurate functional group, imino oxadiazinedione functional group, carbamate functional group, urea functional group, biuret functional group and any combination thereof. The linking group preferably contains isocyanurate functional group, imino oxadiazinedione functional group, biuret functional group, allophanate functional group or uretdione functional group. More preferably, the linking group contains isocyanurate functional group or imino oxadiazinedione functional group. For the sake of clarity, the polyaziridine compound can be obtained from the reaction product of one or more suitable compounds B as defined below with a hybrid isocyanurate (e.g. HDI / IPDI isocyanurate), thereby producing a polyaziridine compound having a linking group consisting of an array of the following consecutive functional groups: a linear CH 12 (i.e., an aliphatic hydrocarbon functional group having 6 carbon atoms), an isocyanurate functional group (cyclic C3N3O3), and
[0084]
[0085] (i.e. an alicyclic hydrocarbon functional group with 9 carbon atoms and an aliphatic hydrocarbon functional group with 1 carbon atom). Even more preferably, the linking group consists of at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group and also an isocyanurate functional group or an iminooxadiazinedione functional group.
[0086] On the linking group, one or more substituents may be present as pendant groups on the linking group, as shown in bold in, for example, the following polyaziridine compounds. These pendant groups are not part of the linking group.
[0087]
[0088] The side groups preferably contain Among them, X, R7, R8, n' and R 10 As described below. In one embodiment of the present invention, the polyaziridine compound comprises one or more linking groups, wherein each of these linking groups links two structural units A in the structural unit A, wherein the linking group consists of: (i) at least two aliphatic hydrocarbon functional groups or at least two alicyclic hydrocarbon functional groups, and (ii) an isocyanurate functional group or an iminooxadiazinedione functional group, and wherein the side group is present on the linking group, wherein the side group has the following structural formula:
[0089]
[0090] n′ is the number of repeating units, and is an integer of 1-50, preferably 2-30, more preferably 5-20.
[0091] X is O or NH, preferably X is O,
[0092] In each repeating unit, R7 and R8 are independently H or CH3,
[0093] R9 is an aliphatic hydrocarbon group, preferably an aliphatic hydrocarbon group containing 1 to 8 carbon atoms, or preferably an alicyclic hydrocarbon group containing 4 to 10 carbon atoms, and
[0094] R 10 contains up to 20 carbon atoms and is an aliphatic, alicyclic or aromatic hydrocarbon group, or a combination thereof. In a preferred embodiment, R7 and R8 are H. In another more preferred embodiment, one of R7 and R8 is H, and the other of R7 and R8 is CH3. 10 Preferably, the polyaziridine compound contains an aliphatic hydrocarbon group (preferably CH3) of 1 to 20 carbon atoms, an alicyclic hydrocarbon group containing 5 to 20 carbon atoms, or an aromatic hydrocarbon group containing 6 to 20 carbon atoms. The presence of the side group causes the viscosity of the polyaziridine compound to decrease and is therefore more easily dispersed in an aqueous medium. In this embodiment, the polyaziridine compound preferably contains 2 structural units A. In this embodiment, the linking group is preferably composed of an array of the following continuous functional groups: a first alicyclic hydrocarbon functional group, an isocyanurate functional group or an iminooxadiazinedione functional group, and a second alicyclic hydrocarbon functional group, and R9 is an alicyclic hydrocarbon group, wherein the first alicyclic hydrocarbon functional group and the second alicyclic hydrocarbon functional group are the same as R9, more preferably, the linking group is composed of an array of the following continuous functional groups: a first aliphatic hydrocarbon functional group, an isocyanurate functional group or an iminooxadiazinedione functional group, and a second aliphatic hydrocarbon functional group, and R9 is an aliphatic hydrocarbon functional group, wherein the first aliphatic hydrocarbon functional group and the second aliphatic hydrocarbon functional group are the same as R9.
[0095] In a preferred embodiment of the present invention, the linking group present in the polyaziridine compound as defined herein is composed of the following functional groups: (i) at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group; and (ii) optionally at least one aromatic hydrocarbon functional group; and (iii) optionally an isocyanurate functional group or an iminooxadiazinedione functional group or an allophanate functional group or a uretdione functional group. Preferably, the linking group present in the polyaziridine compound of the present invention is composed of the following functional groups: (i) at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group; and (ii) optionally at least one aromatic hydrocarbon functional group; and (iii) optionally an isocyanurate functional group or an iminooxadiazinedione functional group. A very suitable way to obtain such polyaziridine compounds is to react a compound B having the following structural formula with a polyisocyanate having aliphatic reactivity:
[0096]
[0097] The term "polyisocyanate with aliphatic reactivity" refers to compounds in which all isocyanate groups are directly bonded to aliphatic or alicyclic hydrocarbon groups, regardless of whether aromatic hydrocarbon groups are also present. The polyisocyanate with aliphatic reactivity may be a mixture of polyisocyanates with aliphatic reactivity. Compounds based on polyisocyanates with aliphatic reactivity have a reduced tendency to yellow over time when compared to similar compounds but based on polyisocyanates with aromatic reactivity. The term "polyisocyanate with aromatic reactivity" is intended to mean compounds in which all isocyanate groups are directly bonded to benzene or naphthalene groups, regardless of whether aliphatic or alicyclic groups are also present. Preferred polyisocyanates with aliphatic reactivity are 1,5-pentamethylene diisocyanate PDI, 1,6-hexamethylene diisocyanate HDI, isophorone diisocyanate IPDI, 4,4′-dicyclohexylmethane diisocyanate H12MDI, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, tetramethylxylene diisocyanate TMXDI (all isomers) and higher molecular weight variants, for example their isocyanurates or iminooxadiazinediones. In this embodiment, preferably, the linking group consists of an array of the following consecutive functional groups: an aliphatic hydrocarbon functional group, an aromatic hydrocarbon functional group and an aliphatic hydrocarbon functional group (for example, when TMXDI is used to prepare the polyaziridine compound), or the linking group consists of an array of the following consecutive functional groups: an alicyclic hydrocarbon functional group, an aliphatic hydrocarbon functional group and an alicyclic hydrocarbon functional group (for example, when H12MDI is used to prepare the polyaziridine compound), or more preferably, the linking group consists of an array of the following consecutive functional groups: an aliphatic hydrocarbon functional group, an isocyanurate functional group or an iminooxadiazinedione functional group and an aliphatic hydrocarbon functional group. Most preferably, in this embodiment, the linking group consists of an array of the following consecutive functional groups: an aliphatic hydrocarbon functional group, an isocyanurate functional group, and an aliphatic hydrocarbon functional group (for example, when the isocyanurate of 1,6-hexamethylene diisocyanate and / or the isocyanurate of 1,5-pentamethylene diisocyanate is used to prepare the polyaziridine compound).
[0098] Preferably, the number of consecutive C atoms and optionally O atoms between the N atom of the carbamate group in the structural unit D and the next N atom present in the connecting chain or being the N atom of the carbamate group of another structural unit D is at most 9, as shown, for example, in the following polyaziridine compounds having 2 or 3 structural units D.
[0099]
[0100]
[0101] The polyaziridine compound preferably contains at least 5 wt%, more preferably at least 5.5 wt%, more preferably at least 6 wt%, more preferably at least 9 wt%, more preferably at least 12 wt% and preferably less than 25 wt%, preferably less than 20 wt% of carbamate bonds. The aziridine equivalent weight of the polyaziridine compound (molecular weight of the polyaziridine compound divided by the number of aziridines present in the polyaziridine compound) is preferably at least 200 Daltons, more preferably at least 230 Daltons and even more preferably at least 260 Daltons, and preferably at most 2500 Daltons, more preferably at most 1000 Daltons and even more preferably at most 500 Daltons.
[0102] The polyaziridine compound is preferably obtained by reacting at least a polyisocyanate with a compound B having the following formula:
[0103]
[0104] wherein the molar ratio of compound B to polyisocyanate is 2 to 6, more preferably 2 to 4, and most preferably 2 to 3, and wherein m, R', R", R1, R2, R3 and R4 are as defined above. The reaction of polyisocyanate with compound B can be carried out by, for example, reacting an equal amount of polyisocyanate with a tin catalyst (e.g. dibutyltin dilaurate) or a bismuth catalyst (e.g. bismuth neodecanoate) at a temperature in the range of from 0°C to 110°C, more preferably from 20°C to 110°C, more preferably from 40°C to 95°C, even more preferably from 60°C to 85°C. Contact with compound B. Solvents such as dimethylformamide DMF, acetone and / or methyl ethyl ketone can be used. The polyisocyanate contains at least 2 isocyanate groups, preferably at least 2.5 isocyanate groups on average, more preferably at least 2.8 isocyanate groups on average. Mixtures of polyisocyanates can also be used as starting materials. Preferred polyisocyanates are polyisocyanates with aliphatic reactivity. The term "polyisocyanate with aliphatic reactivity" refers to compounds in which all isocyanate groups are directly bonded to aliphatic or alicyclic hydrocarbon groups, while those with isocyanate groups are not directly bonded to aliphatic or alicyclic hydrocarbon groups. The polyisocyanate with aliphatic reactivity may be a mixture of polyisocyanates with aliphatic reactivity. Preferred polyisocyanates with aliphatic reactivity are 1,5-pentamethylene diisocyanate PDI, 1,6-hexamethylene diisocyanate HDI, isophorone diisocyanate IPDI, 4,4'-dicyclohexylmethane diisocyanate H12MDI, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, p-tetramethylxylene diisocyanate (p-TMXD I) and their meta-isomers, and higher molecular weight variants, for example their isocyanurates or iminooxadiazinediones or allophanates or uretdione. More preferred polyisocyanates with aliphatic reactivity are 4,4'-dicyclohexylmethane diisocyanate H12MDI, m-TMXDI, isocyanurates or iminooxadiazinediones or allophanates or uretdiones of 1,6-hexamethylene diisocyanate and isocyanurates of 1,5-pentamethylene diisocyanate. Suitable iminooxadiazinedione trimers containing HDI are available from Covestro N3900. Suitable HDI-containing allophanates are available from Covestro XP2860. Suitable uretdione containing HDI is available from Covestro N3400. Suitable HDI-based isocyanurate trimers are available, for example, from Covestro ( N3600), Vencorex (Tolonate TM HDT LV)、AsahiKasei(DuranateTM TPA-100)、Evonik( HT 2500 / LV) and Tosoh( HXRLV). Methods for preparing compound (B) and derivatives are known in the art. For example, the synthesis of 1-(2-methylaziridine-1-yl) propan-2-ol is described by S.Lesniak, M.Rachwalski, S.Jarzynski, E.Obijalska Tetrahedron Asymm.2013, 24 1336-1340. The synthesis of 1-(aziridine-1-yl) propan-2-ol is described by A.Baklien, MVLeeding, J.KolmAust.J.Chem.1968, 21, 1557-1570. The preferred aziridine compounds for preparing compound B are propylene imine and ethyl aziridine. The synthesis of ethyl aziridine is described, for example, in EP0227461B1. The most preferred aziridine compound for preparing compound B is propylene imine.
[0105] Polyaziridine compounds can also be obtained by reacting at least compound B with polyisocyanates as defined above and polyols and / or polyamines. Polyaziridine compounds can also be obtained by reacting polyisocyanates as defined above with polyols and / or polyamines and reacting the compound so obtained with compound B. Polyaziridine compounds can also be obtained by reacting compound B with polyisocyanates and reacting the compound so obtained with polyols and / or polyamines. Polyaziridine compounds can also be obtained by reacting at least compound B with isocyanate-terminated polyurethane and / or polyurethane urea. (Isocyanate-terminated) polyurethane (urea) is obtained by reacting at least one polyol and / or polyamine with at least one polyisocyanate. Preferred polyisocyanates are as described above. Polyol is preferably selected from the group consisting of the following items: polyether polyol, polyester polyol, polythioether polyol, polycarbonate polyol, polyacetal polyol, polyvinyl polyol, polysiloxane polyol and any mixture thereof. More preferably, the polyol is selected from the group consisting of polyether polyols and any mixtures thereof. Preferred polyether polyols are polytetrahydrofuran, polyethylene oxide, polypropylene oxide or any mixtures thereof. More preferred polyether polyols are alkoxy poly(propylene glycol) (preferably methoxy poly(propylene glycol)), poly(propylene glycol) and any mixtures thereof. The polyoxyethylene (-O-CH2-CH2) in the polyaziridine compound x , Polyoxypropylene (-O-CHCH3-CH2-) x or (-O-CH2-CH2-CH2-)x groups and / or polytetrahydrofuran (-O-CH2-CH2-CH2-CH2) xThe amount of the group is preferably at least 6% by weight, more preferably at least 10% by weight, and preferably less than 45% by weight, more preferably less than 40% by weight, and most preferably less than 35% by weight relative to the polyaziridine compound. X represents the average number of added moles of oxyethylene, oxypropylene or tetrahydrofuran, and x is preferably an integer from 5 to 20. The polyamine is preferably selected from the group consisting of polyether polyamines, polyester polyamines, polythioether polyamines, polycarbonate polyamines, polyacetal polyamines, polyethylene polyamines, polysiloxane polyamines, and any mixture thereof. More preferably, the polyamine is selected from the group consisting of polyether polyamines and any mixture thereof. The preferred polyether polyamine is D-230, D-400 and D-2000. The use of polyols is preferred over the use of polyamines. Examples of such polyaziridine compounds are shown below:
[0106]
[0107] Compound B is preferably obtained by reacting at least a non-OH-functional monoepoxide compound with an aziridine compound of the following formula (E):
[0108]
[0109] wherein R1, R2, R3 and R4 are as defined above. The non-OH functional monoepoxide may be a mixture of different non-OH functional monoepoxides. Non-limiting examples of non-OH functional monoepoxides are ethylene oxide, propylene oxide, 2-ethylethylene oxide, n-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, 4-tert-butylphenyl 2,3-epoxypropyl ether (=tert-butylphenyl glycidyl ether), cresol glycidyl ether (ortho or para) and neodecanoic acid glycidyl ester. The non-OH-functional monoepoxide is preferably selected from the group consisting of ethylene oxide (CAS No. 75-21-8), propylene oxide (CAS No. 75-56-9), 2-ethylethylene oxide (CAS No. 106-88-7), n-butyl glycidyl ether (CAS No. 2426-08-6), 2-ethylhexyl glycidyl ether (CAS No. 2461-15-6), neodecanoic acid glycidyl ester (CAS No. 26761-45-5) and any mixtures thereof. More preferably, the non-OH functional monoepoxide is selected from the group consisting of propylene oxide (CAS No. 75-56-9), 2-ethylethylene oxide (CAS No. 106-88-7), n-butyl glycidyl ether (CAS No. 2426-08-6), 2-ethylhexyl glycidyl ether (CAS No. 2461-15-6), neodecanoic acid glycidyl ester (CAS No. 26761-45-5) and any mixture thereof.
[0110] The polyaziridine compound is preferably obtained by a process comprising at least the following steps (i) and (ii):
[0111] (i) reacting an aziridine of formula (E) with an at least non-OH-functional monoepoxide compound to obtain compound B, and
[0112] (ii) reacting compound B with a polyisocyanate.
[0113] Step (i) can be carried out, for example, by contacting one equivalent of the epoxide compound with one equivalent of aziridine at a temperature in the range of from 20° C. to 110° C., more preferably from 40° C. to 95° C., and even more preferably from 60° C. to 85° C. at atmospheric pressure. The reaction of the adduct (compound (B)) obtained in step (i) with a polyisocyanate (step (ii)) can be carried out, for example, by contacting an equal amount of the polyisocyanate with the adduct in the presence of, for example, a tin catalyst (e.g., dibutyltin dilaurate) at a temperature in the range of from 20° C. to 110° C., more preferably from 40° C. to 95° C., at atmospheric pressure.
[0114] Examples of preferred polyaziridine compounds present in the coating composition of the present invention are
[0115]
[0116] and
[0117]
[0118] In a preferred embodiment of the present invention, the polyaziridine compound present in dispersed form in the aqueous coating composition of the present invention has
[0119] a. 2 to 6 structural units according to formula A
[0120]
[0121] wherein R1, R2, R3, R4, R5, R', R", X, Y, m and t and their priorities are as defined above,
[0122] b. one or more linking chains, wherein each of these linking chains connects two structural units A in the structural unit A, wherein the one or more linking chains are preferably as defined above, and
[0123] c. a molecular weight of 600 to 5000 Daltons, preferably at least 700 Daltons, more preferably at least 800 Daltons, even more preferably at least 840 Daltons, most preferably a molecular weight of at least 1000 Daltons, and preferably at most 3800 Daltons, more preferably at most 3600 Daltons, more preferably at most 3000 Daltons, more preferably at most 1600 Daltons, even more preferably at most 1400 Daltons.
[0124] It has been surprisingly found that such polyaziridine compounds have reduced genotoxicity compared to the very commonly used trimethylolpropane tris (2-methyl -1-aziridine propionate). Polyaziridine compounds only show weak positive induced genotoxicity, or do not show genotoxicity at all, that is, they show genotoxicity levels comparable to naturally occurring backgrounds. Therefore, compared to trimethylolpropane tris (2-methyl -1-aziridine propionate), polyaziridine compounds with reduced genotoxicity have more favorable hazardous characteristics than trimethylolpropane tris (2-methyl -1-aziridine propionate), thereby greatly reducing the safety, health and environmental risks associated with its use, resulting in the operation and management burden of polyaziridine compounds with reduced genotoxicity that can be reduced or even removed. Polyaziridine compounds preferably include one or more linking groups, wherein each linking group in the linking group connects two structural units A in the structural unit A, and the linking group and its priority are as defined above.
[0125] In this embodiment, the amount of aziridinyl-functional molecules (also referred to as aziridine-functional molecules) having a molecular weight of less than 250 Daltons, more preferably less than 350 Daltons, even more preferably less than 450 Daltons, even more preferably less than 550 Daltons and even more preferably less than 580 Daltons present in the coating composition according to the invention is preferably less than 5 wt %, more preferably less than 4 wt %, more preferably less than 3 wt %, more preferably less than 2 wt %, more preferably less than 1 wt %, more preferably less than 0.5 wt %, more preferably less than 0.1 wt %, most preferably 0 wt %, relative to the total weight of the coating composition, wherein the molecular weight is determined using LC-MS as described in the experimental section below. Such aziridine-functional molecules may be obtained as by-products during the preparation of polyaziridine compounds as defined herein.
[0126] The average number of aziridinyl groups per aziridinyl-containing molecule in the composition is preferably at least 1.8, more preferably at least 2, more preferably at least 2.2 and preferably less than 10, more preferably less than 6 and most preferably less than 4. Most preferably, the average number of aziridinyl groups per aziridinyl-containing molecule in the composition is from 2.2 to 3.
[0127] Aqueous dispersion
[0128] The aqueous coating composition of the present invention comprises at least two dispersed phases with different compositions, wherein the first dispersed phase comprises particle X, and the particle X comprises a polyaziridine compound as defined herein, and the second dispersed phase comprises particle Y, and the particle Y comprises a carboxylic acid functional polymer that can be crosslinked with a polyaziridine compound as defined herein, with the prerequisite that particle X neither comprises a carboxylic acid functional polymer nor comprises other compounds that can be crosslinked with a polyaziridine compound as defined herein, and particle Y neither comprises a polyaziridine compound nor comprises other compounds that can be crosslinked with the carboxylic acid functional group of a carboxylic acid functional polymer. The aqueous coating composition of the present invention may also comprise particles containing polyaziridine compounds and carboxylic acid functional polymers. Such particles can be produced by the coagulation of particles X and particles Y. Preferably, based on the total amount of the aqueous coating composition, the amount of particles comprising polyaziridine compounds and carboxylic acid functional polymers is less than 30% by weight, preferably less than 20% by weight, more preferably less than 10% by weight, and even more preferably less than 5% by weight.
[0129] The pH of the aqueous coating composition is at least 8. In order to further extend the shelf life of the aqueous dispersion of the present invention, it is beneficial that the pH is at least 8.5, preferably at least 9, more preferably at least 9.5. The pH of the aqueous coating composition is at most 14, preferably at most 13, more preferably at most 12, even more preferably at most 11.5, even more preferably at most 11, because this allows the amount of alkali present in the aqueous coating composition of the present invention to be reduced, while the shelf life of the aqueous coating composition remains sufficiently long. Most preferably, the pH of the aqueous coating composition is in the range of 9.5 to 11.5.
[0130] The coating composition preferably comprises ammonia, secondary amine, tertiary amine, LiOH, NaOH and / or KOH to adjust the pH to the desired value. Preferred amines are ammonia, secondary amines and / or tertiary amines. Examples of such secondary amines are, but are not limited to, diisopropylamine, di-sec-butylamine and di-tert-butylamine. More preferred amines are tertiary amines. Examples of such tertiary amines are, but are not limited to, n-ethylmorpholine, n-methylpiperidine, n,n-dimethylbutylamine, dimethylisopropylamine, dimethyl-n-propylamine, dimethylethylamine, triethylamine, dimethylbenzylamine, n,n-dimethylethanolamine, 2-(diethylamino)ethanol, n,n-dimethylisopropanolamine, 1-dimethylamino-2-propanol, 3-dimethylamino-1-propanol, 2-(dimethylamino)ethanol, 2-[2-(dimethylamino)ethoxy]ethanol. Preferred tertiary amines are n-ethylmorpholine, n-methylpiperidine, n,n-dimethylbutylamine, dimethylisopropylamine, dimethyl-n-propylamine, dimethylethylamine, triethylamine and / or dimethylbenzylamine. Most preferred is triethylamine.
[0131] The amount of water in the aqueous coating composition is based on the total weight of the aqueous coating composition, preferably at least 15 wt %, more preferably at least 20 wt %, more preferably at least 30 wt %, even more preferably at least 40 wt %. The amount of water in the aqueous coating composition is based on the total weight of the aqueous coating composition, preferably at most 90 wt %, preferably at most 85 wt %, more preferably at most 80 wt %, even more preferably at most 70 wt %, even more preferably at most 60 wt %.
[0132] The polyaziridine compound as defined herein is present in the aqueous coating composition in an amount of preferably at least 0.5 wt %, more preferably at least 1 wt %, more preferably at least 1.5 wt %, more preferably at least 2 wt %, even more preferably at least 3 wt %, even more preferably at least 4 wt %, even more preferably at least 5 wt %, even more preferably at least 7 wt %, based on the total solids content of the aqueous coating composition. The polyaziridine compound as defined herein is present in the aqueous coating composition in an amount of preferably at most 50 wt %, preferably at most 30 wt %, more preferably at most 20 wt %, more preferably at most 15 wt %, even more preferably at most 12 wt %, based on the total solids content of the aqueous coating composition.
[0133] The solid content of the coating composition of the present invention is preferably in the range of 5 wt % to 65 wt %. The solid content of the coating composition of the present invention is more preferably at least 10 wt %, even more preferably at least 20 wt %, even more preferably at least 25 wt %, even more preferably at least 35 wt %, and at most 55 wt %, even more preferably at most 50 wt %, even more preferably at most 45 wt %.
[0134] Preferably at least 50% by weight, more preferably at least 85% by weight, more preferably at least 95% by weight, even more preferably at least 99% by weight of the polyaziridine compound as defined herein is present in the crosslinker composition in dispersed form. Therefore, the coating composition of the present invention comprises particles X containing polyaziridine compounds as defined herein. The particles X preferably have an average hydrodynamic diameter based on scattering intensity of 30 nanometers to 500 nanometers, more preferably 50nm to 350nm, even more preferably 110nm to 275nm. The average hydrodynamic diameter of the particles based on scattering intensity can be controlled in a variety of ways. For example, the average hydrodynamic diameter of the particles based on scattering intensity can be controlled during the preparation of the aqueous dispersion of the present invention by using different types of dispersants and / or different amounts of dispersants and / or by applying different shear stresses and / or by applying different temperatures. For example, the average hydrodynamic diameter of the particles based on scattering intensity is inversely proportional to the amount of dispersant used in the preparation of the aqueous dispersion of the present invention; for example, the average hydrodynamic diameter of the particles based on scattering intensity is reduced by increasing the amount of dispersant. For example, the average hydrodynamic diameter of the particles based on the scattered intensity is inversely proportional to the shear stress applied during the preparation of the aqueous dispersion of the present invention; for example, the average hydrodynamic diameter of the particles based on the scattered intensity decreases by increasing the shear stress. Exemplary dispersants include, but are not limited to, ATLAS supplied by Croda TM G-5000、ATLAS TM G-5002L-LQ、Maxemul TM 7101. The coating composition further comprises particles Y comprising a carboxylic acid functional polymer crosslinkable with a polyaziridine compound as defined herein. The particles comprising a carboxylic acid functional polymer preferably have an average hydrodynamic diameter based on scattered intensity of 30 nm to 30,000 nm, more preferably 40 nm to 10,000 nm, even more preferably 40 nm to 3,000 nm, even more preferably 40 nm to 500 nm, even more preferably 60 nm to 260 nm.
[0135] The carboxylic acid functional polymer is preferably selected from the group consisting of polyesters, polycarbonates, polyamides, vinyl polymers, polyacrylates, polymethacrylates, poly(acrylate-co-methacrylates), polyurethanes, poly(urethane-co-acrylates), poly(urethane-co-methacrylates), poly(urethane-co-acrylates-co-methacrylates), polyureas, and mixtures thereof. In one embodiment of the present invention, the preferred crosslinkable carboxylic acid functional polymer is selected from the group consisting of vinyl polymers, polyacrylates, polymethacrylates, poly(acrylate-co-methacrylates), and mixtures thereof. Preferably, the vinyl polymer means a polymer comprising reacted residues of styrene with acrylates and / or methacrylates. In another embodiment, the carboxylic acid functional polymer is selected from the group consisting of polyurethanes, poly(urethane-co-acrylates), poly(urethane-co-methacrylates), poly(urethane-co-acrylates-co-methacrylates), polyureas, and mixtures thereof.
[0136] The acid value of the carboxylic acid functional polymer is preferably 2 mg KOH / gram carboxylic acid functional polymer to 135 mg KOH / gram carboxylic acid functional polymer, more preferably 3 mg KOH / g carboxylic acid functional polymer to 70 mg KOH / g carboxylic acid functional polymer, even more preferably 5 mg KOH / g carboxylic acid functional polymer to 50 mg KOH / g carboxylic acid functional polymer, even more preferably 10 mg KOH / g carboxylic acid functional polymer to 25 mg KOH / g carboxylic acid functional polymer. As used herein, the acid value of the carboxylic acid functional polymer is calculated according to the formula AV=((total molar amount of carboxylic acid components contained in the carboxylic acid functional polymer / gram number of total amount of components contained in the carboxylic acid functional polymer))*56.1*1000) and expressed as mg KOH / gram carboxylic acid functional polymer. Therefore, the acid value of the carboxylic acid functional polymer can be controlled by the molar amount of the carboxylic acid component used to prepare the carboxylic acid functional polymer. If the acid value cannot be properly calculated, the acid value is determined by ASTM D1639-90 (1996) e1.
[0137] The number average molecular weight M of the carboxylic acid functional polymer n The ratio of the number average molecular weight M of the carboxylic acid functional polymer to the acid value of the carboxylic acid functional polymer is preferably at least 150, more preferably at least 300, even more preferably at least 600, even more preferably at least 1000, even more preferably at least 5000, and most preferably at least 15000. As used herein, the number average molecular weight M of the carboxylic acid functional polymer is n Determined by size exclusion chromatography using NMP-MEK.
[0138] The coating composition comprises at least one carboxylic acid functional polymer. The coating composition may comprise a blend of different carboxylic acid functional polymers. The carboxylic acid functional polymer contains carboxylic acid groups and / or carboxylate groups, and the carboxylic acid groups and / or carboxylate groups preferably do not contain covalent bonds that prevent these groups from chemically reacting with the aziridine moiety present in the polyaziridine compound. As used herein, the amount of carboxylic acid groups present in the carboxylic acid functional polymer is the total amount of deprotonated and protonated carboxylic acid groups present in the polymer to be crosslinked (i.e., in the carboxylic acid functional polymer). Therefore, the amount of carboxylic acid groups present in the carboxylic acid functional polymer is the total amount of carboxylate groups and carboxylic acid groups present in the carboxylic acid functional polymer. The polymer to be crosslinked preferably comprises carboxylate groups at least partially neutralized by a base. Preferably, at least part of the base in the base is a volatile base. Preferably, at least a portion of the carboxylic acid groups in the carboxylic acid functional polymer to be crosslinked undergo deprotonation to obtain carboxylate groups. Deprotonation is achieved by neutralizing the carboxylic acid functional polymer with a base. Examples of suitable bases are ammonia, secondary amines, tertiary amines, LiOH, NaOH and / or KOH. Examples of secondary and tertiary amines are as described above. Preferred bases are tertiary amines. Preferred tertiary amines are as described above. Most preferred is triethylamine.
[0139] The coating composition of the present invention preferably comprises the carboxylic acid functional polymer in an amount of at least 3 wt %, preferably at least 5 wt %, more preferably at least 10 wt %, more preferably at least 20 wt %, even more preferably at least 30 wt %, even more preferably at least 40 wt %, even more preferably at least 50 wt %, based on the total weight of the aqueous coating composition. The coating composition of the present invention preferably comprises the carboxylic acid functional polymer in an amount of at most 60 wt %, preferably at most 55 wt %, based on the total weight of the aqueous coating composition.
[0140] Preferably, the amount of aziridine and carboxylic acid groups is selected so that the stoichiometric amount (SA) of aziridine on carboxylic acid groups is 0.1 to 2.0, more preferably 0.2 to 1.5, even more preferably 0.25 to 0.95, most preferably 0.3 to 0.8.
[0141] The polyaziridine compound as defined above is usually obtained in the form of a composition, in which, in addition to the polyaziridine compound, there may also be the remaining starting materials, by-products and / or solvents used in the preparation of the polyaziridine compound. The composition may contain only one polyaziridine compound as defined above, but may also contain more than one polyaziridine compound as defined above. For example, when a mixture of polyisocyanates is used as a starting material, a mixture of polyaziridine compounds is obtained. The coating composition of the present invention can be obtained in the following manner: (i) the polyaziridine compound is dispersed in water and the pH of the aqueous dispersion is adjusted to the desired value, or the polyaziridine compound is dispersed in a mixture of water and at least one alkali, the pH of the mixture being, for example, to obtain an aqueous dispersion with a desired pH value, and (ii) the aqueous dispersion obtained in step (i) is mixed with an aqueous dispersion of a carboxylic acid functional polymer. Polyaziridines can be dispersed in water or in a mixture of water and at least one alkali using techniques well known in the art. The dispersion of polyaziridine compounds can be aided by solvents and / or high shear. Alternatively, the polyaziridine compound may be self-dispersible, in which case the polyaziridine compound may be added directly to the carboxylic acid functional polymer to form separate particles. The polyaziridine may become self-dispersible by incorporating ionic groups, polar nonionic groups (eg, polyalkylene oxide), or any combination thereof.
[0142] The aqueous coating composition can also comprise the gross weight based on the aqueous coating composition, and amount is 35 wt % at the most, preferably 30 wt % at the most, for example 25 wt % at the most, for example 20 wt % at the most, for example 12 wt % at the most, for example 10 wt % at the most, for example 8 wt % at the most, for example 5 wt % at the most, for example 4 wt % at the most, for example 3 wt % at the most, for example 2 wt % at the most, for example 1 wt % at the most, for example 0.5 wt % at the most, for example 0.2 wt % at the most, for example 0.1 wt % organic solvent at the most. The organic solvent can optionally be added before, during and / or after the polyaziridine synthesis. The organic solvent can be used to help polyaziridine compounds to be dispersed in water. If necessary, the organic solvent can be removed from the crosslinker composition by decompression and / or elevated temperature subsequently. Typical organic solvents are glycols, ethers, alcohols, cyclic carbonates, pyrrolidone, dimethyl sulfoxide, n-formyl morpholine, dimethylformamide, amides and ketones. Preferred solvents are glycols (including glycol ethers), ethers, alcohols, cyclic carbonates and ketones.
[0143] Preferably, the dispersion of the polyaziridine compound is carried out in the presence of a dispersant. Therefore, the aqueous coating composition of the present invention preferably comprises a dispersant. In the context of the present invention, a dispersant is a substance that promotes the formation of a dispersion and colloid stabilization. In the present invention, the dispersant is preferably a substance that is non-covalently attached to the polyaziridine compound, and / or the dispersant is a separate molecular component with surface activity. Examples of substances that are non-covalently attached to polyaziridine compounds are amphiphilic compounds containing urea and / or carbamates, such as HEUR thickeners.
[0144] More preferably, the dispersant is at least one separate surface-active molecule component. Preferred separate surface-active molecule components are:
[0145] (i) a polyaziridine compound as defined above, said polyaziridine compound containing functional groups such as sulfonate, sulfate, phosphate and / or phosphonate functional groups, preferably sulfonate and / or phosphonate groups, more preferably sulfonate groups, and / or
[0146] (ii) a polymer, said polymer preferably having a number average molecular weight of at least 2000 Daltons, more preferably at least 2500 Daltons, more preferably at least 3000 Daltons, more preferably at least 3500 Daltons, more preferably at least 4000 Daltons, and preferably at most 1000000 Daltons, more preferably at most 100000, at most 10000 Daltons, as measured by MALDI-ToF-MS as described below.
[0147] More preferred separate surface-active molecular components are polymers having a number average molecular weight of at least 2000 Daltons, more preferably at least 2500 Daltons, more preferably at least 3000 Daltons, more preferably at least 3500 Daltons, more preferably at least 4000 Daltons, and preferably at most 1000000 Daltons, more preferably at most 100000, even more preferably at most 10000 Daltons as measured by MALDI-ToF-MS as described below. Preferred polymers are polyethers, more preferably polyether copolymers, even more preferably polyether block copolymers, even more preferably poly(alkylene oxide) block copolymers, even more preferably poly(ethylene oxide)-co(propylene oxide) block copolymers. Non-limiting examples of preferred separate surface-active molecular dispersants are Atlas Polymers available from Croda. TM G-5000, Maxemul obtained from Croda TM 7101 and / or obtained from BASF P84. The amount of the individual surface active molecular components is generally in the range of 0.1 wt % to 20 wt %, preferably at least 0.5 wt %, more preferably at least 1 wt %, even more preferably at least 2 wt %, even more preferably at least 3 wt %, based on the total weight of the aqueous coating composition.
[0148] The polyaziridine compound containing a functional group (e.g., a sulfonate, sulfate, phosphate and / or phosphonate functional group), preferably a sulfonate functional group, as defined under (i) is preferably obtained by reacting part of the isocyanate groups of a polyisocyanate used to prepare the polyaziridine compound with a hydroxyl or amine functional ion constituent unit (preferably neutralized with an inorganic base). Examples of hydroxyl or amine functional ion constituent units include 2-(cyclohexylamino)ethanesulfonic acid, 3-cyclohexyl-amino)propanesulfonic acid, methyltaurine, taurine, DS-3404. Preferably, sulfonate is used as the hydroxyl or amine functional ion constituent unit.
[0149] The crosslinking efficiency of a crosslinking agent can be assessed by assessing the chemical resistance as defined and determined as described below.
[0150] The storage stability of the aqueous coating composition according to the present invention can be assessed by storing the aqueous coating composition, in particular at elevated temperature (e.g. 50° C.), and assessing the change in viscosity, as defined and measured as described below, of the stored aqueous coating composition, and / or assessing the change in chemical resistance, in particular ethanol resistance, as defined and measured as described below, of the stored coating composition.
[0151] The storage stability of the aqueous coating composition of the present invention at 50° C. is preferably at least 1 week, preferably at least 2 weeks, more preferably at least 3 weeks, even more preferably at least 4 weeks. Storage stability at 50° C. for at least x weeks means that after the aqueous coating composition has been stored at 50° C. for x weeks, (i) the final viscosity of the aqueous coating composition is at most 50 times higher than the initial viscosity, preferably at most 45 times higher than the initial viscosity, more preferably at most 40 times higher than the initial viscosity, more preferably at most 35 times higher than the initial viscosity, more preferably at most 30 times higher than the initial viscosity, more preferably at most 25 times higher than the initial viscosity, more preferably at most 20 times higher than the initial viscosity, more preferably at most 15 times higher than the initial viscosity, more preferably at most 10 times higher than the initial viscosity, most preferably at most 5 times higher than the initial viscosity, and / or (ii) the chemical resistance of the aqueous coating composition as defined and measured as described below is reduced by at most 3 points, preferably at most 2 points, even more preferably at most 1 point. Preferably, storage stable at 50°C for at least x weeks means that after the dispersion has been stored at 50°C for x weeks, (i) the final viscosity of the dispersion is at most 50 times higher, preferably at most 45 times higher, more preferably at most 40 times higher, more preferably at most 35 times higher, more preferably at most 30 times higher, more preferably at most 25 times higher, more preferably at most 20 times higher, more preferably at most 15 times higher, more preferably at most 10 times higher, most preferably at most 5 times higher than the starting viscosity, and (ii) the chemical resistance of the dispersion as defined and determined as described below decreases by at most 3 points, preferably at most 2 points, even more preferably at most 1 point. 'Starting viscosity' of an aqueous coating composition refers to the viscosity of the aqueous coating composition as determined when it is prepared and just before the aqueous coating composition is stored at 50°C (assessed as described below). The 'final viscosity' of the aqueous coating composition refers to the viscosity of the aqueous coating composition determined after the aqueous coating composition has been stored at 50°C for x weeks (assessed as described below).
[0152] The present invention also relates to a method for preparing a coating composition according to the invention, wherein the method comprises: (i) dispersing the polyaziridine compound as defined above in water to obtain an aqueous dispersion and adjusting the pH of the aqueous dispersion to the desired value, or the method comprises dispersing the polyaziridine compound as defined above in a mixture of water and at least one base, the mixture having a pH such that an aqueous dispersion having the desired pH value is obtained, and (ii) mixing the aqueous dispersion obtained in step (i) with an aqueous dispersion of a carboxylic acid-functional polymer. Preferably, the method comprises mixing an alkaline aqueous medium into the polyaziridine compound as defined above, whereby the pH of the alkaline aqueous medium is selected, for example, to obtain an aqueous dispersion having the desired pH value.
[0153] In a preferred embodiment of the present invention, the dispersant is a single surface-active polymer (ii) having a number average molecular weight of at least 2000 Daltons. In this preferred embodiment, the method for preparing the coating composition of the present invention preferably comprises:
[0154] A) optionally but preferably, mixing a polyaziridine compound as defined above in an organic solvent,
[0155] B) mixing the polyaziridine compound as defined above or the solution obtained in step A) with a dispersant to obtain a composition comprising the polyaziridine compound and a dispersant,
[0156] C) mixing water and a base or mixing a basic aqueous medium into the composition comprising the polyaziridine compound and the dispersant to obtain a dispersion
[0157] D) optionally, but preferably, evaporating the organic solvent from the dispersion to obtain a further dispersion, and optionally mixing additional water or an alkaline aqueous medium into the further dispersion to obtain an aqueous dispersion of the polyaziridine compound, and
[0158] E) mixing the aqueous dispersion of the polyaziridine compound obtained in step D) with the aqueous dispersion of the carboxylic acid functional polymer to obtain the coating composition of the present invention.
[0159] Preferably step C) is carried out using a high shear dispersing device.
[0160] The present invention also relates to a substrate with a coating obtained by (i) applying a coating composition as described above to a substrate, and (ii) drying the coating composition by evaporating volatiles. The drying of the coating composition is preferably carried out at a temperature below 160°C, preferably at a temperature below 90°C, more preferably at a temperature below 50°C and most preferably at ambient temperature. The coating composition according to the present invention can be applied to any kind of substrate, such as wood, leather, concrete, textiles, plastics, vinyl flooring, glass, metal, ceramics, paper, wood-plastic composites, glass fiber reinforced materials. The thickness of the dry coating on the substrate is preferably 1 micron to 200 microns, more preferably 5 microns to 150 microns, and most preferably 15 microns to 90 microns. In the case where the coating composition is an ink composition, the thickness of the dry ink is preferably 0.005 microns to 35 microns, more preferably 0.05 microns to 25 microns, and most preferably 4 microns to 15 microns.
[0161] The present invention is further defined by a set of exemplary embodiments as listed below. Unless otherwise stated herein or if it is obvious to a skilled person that it is not technically feasible, any of the embodiments, aspects and preferred features or ranges as disclosed in this application may be combined in any combination.
[0162] [1] An aqueous coating composition comprising a polyaziridine compound and a carboxylic acid functional polymer, wherein
[0163] (i) the composition is an aqueous dispersion having a pH range of 8 to 14,
[0164] (ii) the aqueous dispersion comprises particles X and particles Y, wherein the particles X comprise a polyaziridine compound and the particles Y comprise a carboxylic acid functional polymer, and
[0165] (iii) the polyaziridine compound has:
[0166] a) 2 to 6 of the following structural units A:
[0167]
[0168] in
[0169] R1 is H,
[0170] R2 and R4 are independently selected from H or an aliphatic hydrocarbon group containing 1 to 4 carbon atoms,
[0171] R3 is an aliphatic hydrocarbon group containing 1 to 4 carbon atoms,
[0172] m is an integer from 1 to 6,
[0173] R' and R" are according to (1) or (2):
[0174] (1) R'=H or an aliphatic hydrocarbon group containing 1 to 14 carbon atoms; and R"=H, an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, an alicyclic hydrocarbon group containing 5 to 12 carbon atoms, an aromatic hydrocarbon group containing 6 to 12 carbon atoms, CH2-O-(C=O)-R"', CH2-OR"" or CH2-(OCR""'HCR""'H) n -OR""", wherein R"' is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms and R"" is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms or an aromatic hydrocarbon group containing 6 to 12 carbon atoms, n is 1 to 35, R""' is independently H or an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, and R""" is an aliphatic hydrocarbon group containing 1 to 4 carbon atoms,
[0175] (2) R' and R" together form a saturated alicyclic hydrocarbon group containing 5 to 8 carbon atoms,
[0176] t is an integer from 0 to 3,
[0177] R5 is H or CH3,
[0178] X and Y are according to (I), (II) or (III):
[0179] (I) X and Y are both N-R6;
[0180] (II) X is O and Y is N-R6;
[0181] (III) X is N-R6 and Y is O,
[0182] wherein R6 is H or a straight or branched hydrocarbon group containing 1 to 4 carbon atoms;
[0183] b) one or more connecting chains, wherein each of the connecting chains connects two of the structural units A; and
[0184] c) A molecular weight in the range of 500 Daltons to 10,000 Daltons.
[0185] [2] The aqueous coating composition according to embodiment 1, wherein R2 is H, R3 is C2H5 and R4 is H.
[0186] [3] The aqueous coating composition according to embodiment 1, wherein R2 is H, R3 is CH3 and R4 is H.
[0187] [4] The aqueous coating composition according to embodiment 1, wherein R2 is H, R3 is CH3 and R4 is CH3.
[0188] [5] The aqueous coating composition according to any one of embodiments [1] to [4], wherein m is 1.
[0189] [6] The aqueous coating composition according to any one of embodiments [1] to [5], wherein t is 0 or 1.
[0190] [7] The aqueous coating composition according to any one of embodiments [1] to [6], wherein R6 is H.
[0191] [8] The aqueous coating composition according to any one of embodiments [1] to [4], wherein X is O, Y is NH, m is 1 and t is 0.
[0192] [9] An aqueous coating composition according to any one of embodiments [1] to [8], wherein the connecting chain consists of 4 to 300 atoms, more preferably 5 to 250 atoms, and most preferably 6 to 100 atoms, and the connecting chain is a collection of covalently linked atoms, the collection of atoms consisting of i) carbon atoms, ii) carbon and nitrogen atoms, or iii) carbon, oxygen and nitrogen atoms.
[0193]
[10] The aqueous coating composition according to any one of embodiments [1] to [9], wherein the polyaziridine compound contains 2 or 3 structural units A.
[0194]
[11] An aqueous coating composition according to any one of embodiments [1] to
[10] , wherein R' and R" are according to (1) or (2):
[0195] (1) R'=H or an alkyl group containing 1 to 2 carbon atoms; R"=H, an aliphatic hydrocarbon group containing 1 to 4 carbon atoms, CH2-O-(C=O)-R"', CH2-OR"" or CH2-(OCR""'HCR""'H) n -OR""", wherein R"' is an alkyl group containing 1 to 14 carbon atoms and R"" is an alkyl group containing 1 to 14 carbon atoms, n is 1 to 35, R""' is independently H or methyl, and R""" is an alkyl group containing 1 to 4 carbon atoms;
[0196] (2) R' and R" together form a saturated alicyclic hydrocarbon group containing 5 to 8 carbon atoms.
[0197]
[12] An aqueous coating composition according to any one of embodiments [1] to
[10] , wherein R' is H and R"=an alkyl group containing 1 to 4 carbon atoms, CH2-O-(C=O)-R"', CH2-OR"", wherein R"' is an alkyl group containing 3 to 12 carbon atoms and R"" is an alkyl group containing 1 to 14 carbon atoms.
[0198]
[13] An aqueous coating composition according to any one of embodiments [1] to
[12] , wherein the polyaziridine compound comprises one or more linking groups, wherein each of these linking groups links two structural units A in the structural unit A, wherein the linking group is composed of at least one functional group selected from the group consisting of: an aliphatic hydrocarbon functional group (preferably containing 1 to 8 carbon atoms), an alicyclic hydrocarbon functional group (preferably containing 4 to 10 carbon atoms), an aromatic hydrocarbon functional group (preferably containing 6 to 12 carbon atoms), an isocyanurate functional group, an iminooxadiazinedione functional group, an ether functional group, an ester functional group, an amide functional group, a carbonate functional group, a carbamate functional group, a urea functional group, a biuret functional group, an allophanate functional group, a uretdione functional group, and any combination thereof.
[0199]
[14] An aqueous coating composition according to embodiment
[13] , wherein the linking group consists of at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group and optionally at least one aromatic hydrocarbon functional group and optionally an isocyanurate functional group or an iminooxadiazinedione functional group.
[0200]
[15] The aqueous coating composition according to embodiment
[13] , wherein the linking group consists of at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group and an isocyanurate functional group or an iminooxadiazinedione functional group.
[0201]
[16] An aqueous coating composition according to any one of embodiments [1] to
[12] , wherein the polyaziridine compound comprises one or more linking groups, wherein each of the linking groups links two of the structural units A, wherein the linking group consists of (i) at least two aliphatic hydrocarbon functional groups and (ii) an isocyanurate functional group or an iminooxadiazinedione functional group, and wherein a pendant group is present on the linking group, wherein the pendant group has the following structural formula:
[0202]
[0203] n′ is the number of repeating units, and is an integer of 1-50, preferably 2-30, more preferably 5-20.
[0204] X is O or NH, preferably X is O,
[0205] In each repeating unit, R7 and R8 are independently H or CH3,
[0206] R9 is an aliphatic hydrocarbon group, preferably containing 1 to 8 carbon atoms, and
[0207] R 10Preferred are aliphatic hydrocarbon groups (preferably CH 3 ) containing 1 to 20 carbon atoms, alicyclic hydrocarbon groups containing 5 to 20 carbon atoms, or aromatic hydrocarbon groups containing 6 to 20 carbon atoms.
[0208]
[17] An aqueous coating composition, wherein the composition is an aqueous coating composition having a pH range of 8 to 14 and comprising a polyaziridine compound in dispersed form and a carboxylic acid functional polymer in dispersed form, wherein the polyaziridine compound has 2 to 6 structural units A as defined in embodiment [1], wherein R1, R2, R3, R4, R', R", m, t, R5, X and Y are as defined in any one of embodiments [1] to
[12] , wherein the polyaziridine compound has a molecular weight of 500 Daltons to 10,000 Daltons, and wherein the polyaziridine compound further comprises one or more A plurality of linking groups, wherein each of these linking groups connects two structural units A in the structural unit A, wherein the linking group is composed of at least one functional group selected from the group consisting of: an aliphatic hydrocarbon functional group (preferably containing 1 to 8 carbon atoms), an alicyclic hydrocarbon functional group (preferably containing 4 to 10 carbon atoms), an aromatic hydrocarbon functional group (preferably containing 6 to 12 carbon atoms), an isocyanurate functional group, an iminooxadiazinedione functional group, an ether functional group, an ester functional group, an amide functional group, a carbonate functional group, a carbamate functional group, a urea functional group, a biuret functional group, an allophanate functional group, a uretdione functional group, and any combination thereof.
[0209]
[18] The aqueous coating composition according to any one of embodiments [1] to
[17] , wherein the structural unit A is according to the following structural formula D:
[0210]
[0211]
[19] An aqueous coating composition according to any one of embodiments [1] to
[18] , wherein the polyaziridine compound is obtained by reacting at least a polyisocyanate with a compound B having the following structural formula:
[0212]
[0213] The molar ratio of compound B to polyisocyanate is 2 to 6, more preferably 2 to 4, most preferably 2 to 3, and m, R', R", R1, R2, R3 and R4 are as defined in the above embodiments.
[0214]
[20] The aqueous coating composition according to embodiment
[19] , wherein the polyisocyanate is a polyisocyanate having aliphatic reactivity.
[0215]
[21] An aqueous coating composition according to embodiment
[19] or
[20] , wherein compound B is obtained by reacting at least a non-OH functional monoepoxide compound with an aziridine having the following structural formula:
[0216]
[0217] wherein R1, R2, R3 and R4 are as defined in the above embodiments.
[0218]
[22] An aqueous coating composition according to embodiment
[21] , wherein the non-OH functional monoepoxide compound is selected from the group consisting of ethylene oxide, propylene oxide, 2-ethylethylene oxide, n-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, neodecanoic acid glycidyl ester and any mixture thereof.
[0219]
[23] An aqueous coating composition according to any one of embodiments
[19] to
[22] , wherein the polyaziridine compound is a reaction product of at least compound (B), a polyisocyanate, and an alkoxy poly(propylene glycol) and / or a poly(propylene glycol).
[0220]
[24] An aqueous coating composition according to any one of embodiments [1] to
[23] , wherein the molecular weight of the polyaziridine compound is 600 Daltons to 5000 Daltons, more preferably the molecular weight of the polyaziridine compound is at least 800 Daltons, even more preferably at least 840 Daltons, even more preferably at least 1000 Daltons, and preferably at most 3800 Daltons, more preferably at most 3600 Daltons, more preferably at most 3000 Daltons, more preferably at most 1600 Daltons, even more preferably at most 1400 Daltons.
[0221]
[25] An aqueous coating composition according to any one of embodiments [1] to
[24] , wherein the aqueous coating composition comprises aziridine functional molecules having a molecular weight of less than 250 Daltons, more preferably less than 350 Daltons, even more preferably less than 450 Daltons, even more preferably less than 550 Daltons and even more preferably less than 580 Daltons, the amount of aziridine functional molecules being preferably less than 5 wt %, more preferably less than 4 wt %, more preferably less than 3 wt %, more preferably less than 2 wt %, more preferably less than 1 wt %, more preferably less than 0.5 wt %, more preferably less than 0.1 wt %, most preferably 0 wt %, based on the total weight of the aqueous coating composition, wherein the molecular weight is determined using LC-MS as described in the specification.
[0222]
[26] The aqueous coating composition according to any one of embodiments [1] to
[25] , wherein the pH of the aqueous coating composition is at least 8.5, more preferably at least 9, and more preferably at least 9.5.
[0223]
[27] An aqueous coating composition according to any one of embodiments [1] to
[26] , wherein the pH of the aqueous coating composition is at most 14, more preferably at most 13, even more preferably at most 12, even more preferably at most 11.5.
[0224]
[28] The aqueous coating composition according to any one of embodiments [1] to
[27] , wherein the pH of the aqueous coating composition is in the range of 9.5 to 11.5.
[0225]
[29] An aqueous coating composition according to any one of embodiments [1] to
[28] , wherein the aqueous coating composition comprises ammonia, a secondary amine, a tertiary amine, LiOH, NaOH and / or KOH to adjust the pH to a desired value, preferably the aqueous coating composition comprises a tertiary amine selected from the following: n-ethylmorpholine, n-methylpiperidine, n,n-dimethylbutylamine, dimethylisopropylamine, dimethyl-n-propylamine, dimethylethylamine, triethylamine and / or dimethylbenzylamine, most preferably comprising triethylamine to adjust the pH to a desired value.
[0226]
[30] An aqueous coating composition according to any one of embodiments [1] to
[29] , wherein the amount of water in the aqueous coating composition is at least 15 wt %, preferably at least 20 wt %, more preferably at least 30 wt %, and even more preferably at least 40 wt %, based on the total weight of the aqueous coating composition.
[0227]
[31] An aqueous coating composition according to any one of embodiments [1] to
[30] , wherein the amount of water in the aqueous coating composition is at most 95 wt %, preferably at most 90 wt %, more preferably at most 85 wt %, more preferably at most 80 wt %, even more preferably at most 70 wt %, even more preferably at most 60 wt %, based on the total weight of the aqueous coating composition.
[0228]
[32] An aqueous coating composition according to any one of embodiments [1] to
[31] , wherein the amount of the polyaziridine compound in the aqueous coating composition is at least 0.5 wt %, preferably at least 1 wt %, more preferably at least 1.5 wt %, more preferably at least 2 wt %, even more preferably at least 3 wt %, even more preferably at least 4 wt %, even more preferably at least 5 wt %, based on the total solid content of the aqueous coating composition.
[0229]
[33] An aqueous coating composition according to any one of embodiments [1] to
[32] , wherein the amount of the polyaziridine compound in the aqueous coating composition is at most 50 wt %, preferably at most 30 wt %, more preferably at most 20 wt %, even more preferably at most 15 wt %, even more preferably at most 12 wt %, based on the total solid content of the aqueous coating composition.
[0230]
[34] An aqueous coating composition according to any one of embodiments [1] to
[33] , wherein the aqueous coating composition comprises a carboxylic acid-functional polymer in an amount of at least 3 wt %, preferably at least 5 wt %, more preferably at least 10 wt %, more preferably at least 20 wt %, even more preferably at least 30 wt %, even more preferably at least 40 wt %, even more preferably at least 50 wt %, based on the total weight of the aqueous coating composition.
[0231]
[35] An aqueous coating composition according to any one of embodiments [1] to
[34] , wherein the aqueous coating composition comprises a carboxylic acid functional polymer in an amount of up to 60 wt %, preferably up to 55 wt %, based on the total weight of the aqueous coating composition.
[0232]
[36] An aqueous coating composition according to any one of embodiments [1] to
[35] , wherein the amount of aziridine groups and the amount of carboxylic acid groups are selected so that the stoichiometric amount (SA) of aziridine groups on the carboxylic acid groups is 0.1 to 2.0, more preferably 0.2 to 1.5, even more preferably 0.25 to 0.95, and most preferably 0.3 to 0.8.
[0233]
[37] An aqueous coating composition according to any one of embodiments [1] to
[36] , wherein the aqueous coating composition further comprises an organic solvent in an amount of up to 35 wt %, preferably up to 30 wt %, for example up to 25 wt %, for example up to 20 wt %, for example up to 12 wt %, for example up to 10 wt %, for example up to 8 wt %, for example up to 5 wt %, for example up to 4 wt %, for example up to 3 wt %, for example up to 2 wt %, for example up to 1 wt %, for example up to 0.5 wt %, for example up to 0.2 wt %, for example up to 0.1 wt %, based on the total weight of the aqueous coating composition.
[0234]
[38] An aqueous coating composition according to any one of embodiments [1] to
[37] , wherein the solid content of the aqueous coating composition is at least 5 wt %, preferably at least 10 wt %, even more preferably at least 20 wt %, even more preferably at least 25 wt %, even more preferably at least 35 wt % and at most 55 wt %, more preferably at most 50 wt % and even more preferably at most 45 wt %.
[0235]
[39] An aqueous coating composition according to any one of embodiments [1] to
[38] , wherein the particles X have an average hydrodynamic diameter based on scattering intensity of 30 nm to 500 nm, preferably 30 nm to 350 nm, more preferably 110 nm to 275 nm.
[0236]
[40] An aqueous coating composition according to any one of embodiments [1] to
[39] , wherein the particles Y have an average hydrodynamic diameter based on scattering intensity of 30 nm to 30,000 nm, more preferably 40 nm to 10,000 nm, even more preferably 40 nm to 3,000 nm, even more preferably 40 nm to 500 nm, even more preferably 60 nm to 260 nm.
[0237]
[41] An aqueous coating composition according to any one of embodiments [1] to
[40] , wherein the carboxylic acid functional polymer is selected from the group consisting of polyesters, polycarbonates, polyamides, vinyl polymers, polyacrylates, polymethacrylates, poly(acrylate-co-methacrylates), polyurethanes, poly(urethane-co-acrylates), poly(urethane-co-methacrylates), poly(urethane-co-acrylates-co-methacrylates), polyureas, and mixtures thereof.
[0238]
[42] An aqueous coating composition according to any one of embodiments [1] to
[40] , wherein the carboxylic acid functional polymer is selected from the group consisting of vinyl polymers, polyacrylates, polymethacrylates, poly(acrylate-co-methacrylates), and mixtures thereof.
[0239]
[43] An aqueous coating composition according to any one of embodiments [1] to
[40] , wherein the carboxylic acid functional polymer is selected from the group consisting of polyurethanes, poly(urethane-co-acrylates), poly(urethane-co-methacrylates), poly(urethane-co-acrylates-co-methacrylates), polyureas, and mixtures thereof.
[0240]
[44] An aqueous coating composition according to any one of embodiments [1] to
[43] , wherein the acid value of the carboxylic acid functional polymer is from 2 mg KOH / g carboxylic acid functional polymer to 135 mg KOH / g carboxylic acid functional polymer, more preferably from 3 mg KOH / g carboxylic acid functional polymer to 70 mg KOH / g carboxylic acid functional polymer, even more preferably from 5 mg KOH / g carboxylic acid functional polymer to 50 mg KOH / g carboxylic acid functional polymer, even more preferably from 10 mg KOH / g carboxylic acid functional polymer to 25 mg KOH / g carboxylic acid functional polymer.
[0241]
[45] An aqueous coating composition according to any one of embodiments [1] to
[44] , wherein the carboxylic acid functional polymer comprises carboxylate groups at least partially neutralized by a volatile tertiary amine.
[0242]
[46] The aqueous coating composition according to any one of embodiments [1] to
[45] , wherein the number average molecular weight M of the carboxylic acid functional polymer is n The ratio to the acid value is at least 150, more preferably at least 300, even more preferably at least 600, even more preferably at least 1000, even more preferably at least 5000, and most preferably at least 15000.
[0243]
[47] The aqueous coating composition according to any one of embodiments [1] to
[46] , wherein the aqueous coating composition contains a dispersant.
[0244]
[48] An aqueous coating composition according to any one of embodiments [1] to
[47] , wherein the aqueous coating composition contains a separate surface-active molecular component as a dispersant, and the amount of the separate surface-active molecular component is in the range of 0.1 wt % to 20 wt %, based on the total weight of the aqueous coating composition, preferably at least 0.5 wt %, more preferably at least 1 wt %, even more preferably at least 2 wt %, even more preferably at least 3 wt %.
[0245]
[49] An aqueous coating composition according to embodiment
[48] , wherein the dispersant is a polymer having a number average molecular weight of at least 2000 Daltons, more preferably at least 2500 Daltons, more preferably at least 3000 Daltons, more preferably at least 3500 Daltons, more preferably at least 4000 Daltons, and preferably at most 1000000 Daltons, more preferably at most 100000 Daltons, at most 10000 Daltons.
[0246]
[50] An aqueous coating composition according to any one of embodiments
[47] to
[49] , wherein the dispersant is a polyether, more preferably a polyether copolymer, even more preferably a polyether block copolymer, even more preferably a poly(alkylene oxide) block copolymer, even more preferably a poly(ethylene oxide)-co-poly(propylene oxide) block copolymer.
[0247]
[51] The aqueous coating composition according to any one of embodiments [1] to
[50] , wherein the aqueous coating composition is self-crosslinkable.
[0248]
[52] An aqueous coating composition according to any one of embodiments [1] to
[51] , wherein the aqueous coating composition has a storage stability at 50° C. of at least 1 week, preferably at least 2 weeks, more preferably at least 3 weeks, and even more preferably at least 4 weeks.
[0249]
[54] An aqueous coating composition according to any one of embodiments [1] to
[53] , wherein the particle X contains neither a carboxylic acid functional polymer nor other compounds that can be cross-linked with the polyaziridine compound, and the particle Y contains no polyaziridine compound, preferably the particle Y contains neither the polyaziridine compound nor other cross-linking compounds that can cross-link with the carboxylic acid functional groups of the carboxylic acid functional polymer, and more preferably the particle Y contains neither the polyaziridine compound nor other cross-linking compounds.
[0250]
[53] A method for preparing an aqueous coating composition according to any one of embodiments [1] to
[52] , wherein the method comprises dispersing the polyaziridine compound as defined in any of the preceding embodiments in water to obtain an aqueous dispersion and adjusting the pH of the aqueous dispersion to a desired value, or wherein the method comprises dispersing the polyaziridine compound as defined in any of the preceding embodiments in a mixture of water and at least one base, the mixture having a pH such that an aqueous dispersion having a desired pH value is obtained.
[0251]
[54] A method according to embodiment
[53] , wherein the method comprises mixing a basic aqueous medium into a polyaziridine compound as defined in any of the preceding embodiments, wherein the pH of the basic aqueous medium is selected to obtain an aqueous dispersion having a desired pH value, and (ii) mixing the aqueous dispersion obtained in step (i) with an aqueous dispersion of a carboxylic acid-functional polymer.
[0252]
[55] A method according to embodiment
[54] , wherein the method comprises
[0253] A) optionally but preferably mixing a polyaziridine compound as defined in any one of the preceding embodiments in an organic solvent,
[0254] B) mixing the polyaziridine compound as defined in any one of the preceding embodiments or the solution obtained in step A) with a dispersant to obtain a composition comprising a polyaziridine compound and a dispersant,
[0255] C) mixing water and a base or mixing a basic aqueous medium into the composition comprising the polyaziridine compound and the dispersant to obtain a dispersion
[0256] D) optionally, but preferably, evaporating the organic solvent from the dispersion to obtain a further dispersion, and optionally mixing additional water or an alkaline aqueous medium into the further dispersion to obtain an aqueous dispersion of the polyaziridine compound, and
[0257] E) mixing the aqueous dispersion of the polyaziridine compound obtained in step D) with the aqueous dispersion of the carboxylic acid functional polymer to obtain the coating composition according to any one of embodiments [1] to
[52] .
[0258]
[56] A substrate having a coating, the coating being obtained by (i) applying the aqueous coating composition according to any one of embodiments [1] to
[52] onto a substrate and (ii) drying the aqueous coating composition by evaporating volatiles.
[0259] The invention will now be illustrated by reference to the following examples. Unless otherwise indicated, all parts, percentages and ratios are by weight.
[0260] Particle size measurement
[0261] The average hydrodynamic diameter of the particles based on the scattered intensity was determined using a method derived from the ISO 22412:2017 standard with a Malvern Zetasizer Nano S90 DLS instrument, which was operated under the following settings: as a material, polystyrene latex was defined as having an RI of 1.590 at 25°C and an absorbance of 0.10 for a demineralized water continuous medium with a viscosity of 0.8812 cP and an RI of 1.332. The measurements were performed in a DTS0012 disposable cuvette obtained from Malvern Instruments (Malvern, Worcestershire, United Kingdom). The measurements were performed at a backscattering angle of 173°, averaging 3 measurements after 120 seconds of equilibrium, consisting of 10-15 sub-runs - optimized by the machine itself. The focus of the laser was located at a fixed position of 4.65 cm, and the data were analyzed using a general data fitting process. The sample was prepared by diluting 0.05 g (1 drop) of sample dispersion in about 5 mL of demineralized water. If the sample still looks turbid, dilute further with distilled water until the sample becomes almost clear. This method is suitable for determining particle sizes from 2nm to 3μm.
[0262] pH Measurement
[0263] The pH of the samples was determined according to ISO 976:2013. The samples were measured at 23° C. using a Metrohm 691 pH meter equipped with a combined glass electrode and a PT-1000 temperature sensor. The pH meter was calibrated before use using buffer solutions of pH 7.00 and 9.21.
[0264] NCO determination
[0265] The NCO content of the sample was determined according to ASTM D2572-19. In this procedure, the sample is reacted with an excess of n-dibutylamine. The excess n-dibutylamine is then back-titrated with standard 1N hydrochloric acid (HCl). The difference in titration volume between the sample and the blank is a measure of the isocyanate content based on solids, according to the following formula: % NCO 固体 =[(Vb-Vm)*N*4.2] / (A*s / 100), where %NCO 固体 is the isocyanate content in solids, Vb is the volume of HCl used in the blank, Vm is the volume of HCl used in the sample, N is the normality of the HCl solution, A is the sample weight in grams, and s is the solids content of the sample in %. The measurements were performed in duplicate on a Metrohm 702SM Titrino titrator using a potentiometric endpoint (if the difference between the two replicates was <0.1% NCO , then accept the measurement result).
[0266] AV determination
[0267] The solid matter acid value (AV) of the sample is determined based on the ASTM D1639-90 (1996) e1 standard. In this procedure, a sample dissolved in a good solvent is titrated with a potassium hydroxide alcohol solution of known concentration (KOH). The difference in titration volume between the sample and the blank is a measure of the solid acid value, according to the following formula: AV = [(Vblank-Vsample)*N KOH *56.1] / (W*S / 100), where AV is the solid acid value in mg KOH / g solid matter, Vblank is the volume of KOH solution used in the blank, Vsample is the volume of KOH solution used in the sample, and N KOH is the normality of the KOH solution, W is the sample weight in grams, S is the solid content of the sample in %. The measurements were performed in duplicate on a Metrohm 702SM Titrino titrator using a potentiometric endpoint (the measurement result was accepted if the difference between the two replicates was <0.1 mg KOH / g solid matter).
[0268] Chemical resistance
[0269] Chemical resistance test based on DIN 68861-1:2011-01.
[0270] Unless otherwise stated, chemical resistance tests are as follows:
[0271] The coating compositions were processed as described in the examples and then cast using a wire rod coater at a wet layer thickness of 100 μm. After casting, the films were dried at 25°C for 1 hour and then annealed at 50°C for 16 hours. Subsequently, a piece of cotton wool was soaked in 1:1 ethanol: demineralized water (by weight) and placed on the film for 60 minutes (unless otherwise stated). After removal of the cotton wool and overnight recovery, the spots were scored according to the following scale:
[0272] 1 Complete coating degradation
[0273] 2 Structural damage to the coating
[0274] 3 Severe markings on the coating, visible from multiple directions
[0275] 4 Slight marks on the coating, visible from certain angles
[0276] 5 No marking or gloss change observed
[0277] Viscosity measurement:
[0278] Apparent viscosity was determined according to ISO 2555:2018. Measurements were performed at 23°C on a Brookfield DVE-LV viscometer (single cylinder geometry) at 60 rpm. Spindle was selected from S62, S63 or S64, using the lowest numbered spindle (i.e., largest spindle) that produced a torque reading between 10% and 100%.
[0279] Size Exclusion Chromatography Using NMP-MEK
[0280] The molecular weight distribution was measured using an Alliance separation module (Waters e2695), which includes a pump, an autosampler, a degasser, and a column oven. The eluent was 80% n-methylpyrrolidone (NMP) / 20% methyl ethyl ketone (MEK), and 0.01M lithium bromide was added. The injection volume was 150 μl. The flow rate was set to 1.0 ml / min. Three PL Mixed B (Polymer Laboratories) with guard columns (5 μm PL) were applied at a temperature of 70°C. Detection was performed at 50°C using a differential refractive index detector (Waters 2414). The sample was dissolved in the eluent using a concentration of 5 mg polymer / mL solvent. Solubility was determined with a laser pen after stabilization at room temperature for 24 hours; if any scattering was visible, the sample was first filtered. Calculations were performed using eight polystyrene standards (polymer standards service) ranging from 160 Daltons to 1,737,000 Daltons. Calculations were performed using Empower software (Waters) with a third order calibration curve. The molar masses obtained are polystyrene equivalent molar masses (Daltons).
[0281] T by DSC g Measurement
[0282] The glass transition temperature (T) of the polymers was measured by differential scanning calorimetry (DSC) at a heating rate of 10°C / min in a N2 atmosphere at a flow rate of 50 mL / min on a TA Instruments Discovery DSC 250 instrument according to the following method: g ): Weigh 5±0.5 mg of sample and place in a DSC chamber at a temperature between 20°C and 25°C. Cool the sample to -120°C and equilibrate at this temperature; after equilibration, heat the sample from -120°C to 160°C at a heating rate of 5°C / min; keep the sample at this temperature for 2 minutes and then cool it to -120°C at a cooling rate of 20°C / min; once the sample reaches -120°C, maintain the temperature for 5 minutes; then heat the sample from -120°C to 220°C at a heating rate of 5°C / min (thermogram A). T is measured from this last thermogram (thermogram A). g , for T g The half width of the steps in the observed DSC signal (DSC thermogram, heat flow versus temperature). The DSC signal processing and T were performed using TRIOS software version 5.0 provided by TA instruments. g Determination of.
[0283] Analysis of low molecular weight fractions by LC-MS
[0284] LC system: Agilent 1290 Infinity II; Detector No. 1: Agilent 1290 Infinity IIPDA; Detector No. 2: Agilent iFunnel 6550 Q-TOF-MS.
[0285] LC-MS analysis of the low molecular weight fraction was performed using the following procedure. A methanol solution of approximately 100 mg / kg of the material was prepared gravimetrically and stirred. 0.5 μl of this solution was injected into a UPLC equipped with ESI-TOF-MS detection. The column used was a 100×2.1 mm, 1.8 um, Waters HSS T3 C18 operated at 40°C. The flow rate was 0.5 ml.min -1. The solvent used was 10 mM NH4CH3COO aqueous solution (eluent A), acetonitrile (B) and THF (C) set to pH 9.0 with NH3. Two binary gradients from 80 / 20A / B to 1 / 99A / B in 10 minutes and from 1 / 99A / B to 1 / 49 / 50A / B / C in 5 minutes were applied, after which the starting condition (80 / 20A / B) was applied. Assuming that all components have linear MS responses in all response ranges and that the ionization efficiency of all components is equal, the total ion current signal is integrated. In the case of co-elution, the extracted ion chromatogram of the specific species is integrated. The integral signal of the specific low molecular weight peak is divided by the total integral sample signal to produce the score of the low molecular weight substance.
[0286] MALDI-ToF-MS
[0287] All MALDI-ToF-MS spectra are obtained using Bruker Ultraflextreme MALDI-ToF mass spectrometer. The instrument is equipped with a Nd:YAG laser and a collision cell (not used for these samples) emitted at 1064nm. Use a reflector, use the highest resolution mode (scope of 60-7000m / z) providing accurate mass to obtain spectrum in positive ion mode. Use cesium triiodide (scope of 0.3-3.5kDa) to carry out mass calibration (calibration method: IAV molecular characterization, code MC-MS-05). The laser energy is 20%. Sample is dissolved in THF with about 50mg / mL. The matrix used is: DCTB (trans 2-[3-(4-tert-butylphenyl)-2-methyl-2-propenyl] malononitrile), CAS number 300364-84-5. Prepare matrix solution by dissolving 20mg in 1mL THF.
[0288] Sodium iodide was used as salt (NaI, CAS No. 7681-82-5); 10 mg was dissolved in 1 ml THF and one drop of MeOH was added. The ratio of sample: matrix: salt = 10:200:10 (μl), after mixing, 0.5 μl was spotted onto a MALDI plate and air-dried. The peak measured in the MALDI spectrum is the sodium adduct of the polyaziridine compound, and in the context of this specification, the molecular weight (MW) of the polyaziridine compound corresponds to MW = observed [M+M 阳离子 ]–M 阳离子 , where the observed [M+M 阳离子 ] is the MALDI-TOF MS peak, and M 阳离子 is the exact mass of the cation used to prepare the adduct (in this case, M for sodium 阳离子= 23.0 Da). Polyaziridine compounds can be identified by comparing the MW to the exact molecular mass of the theoretical structure (ie the sum of the non-isotopic average atomic masses of its constituent atoms), using a maximum deviation of 0.6 Da.
[0289] Genotoxicity testing
[0290] pass The ToxTracker assay (Toxys, Leiden, the Netherlands) assesses genotoxicity. The ToxTracker assay is a set of several validated green fluorescent protein (GFP)-based mouse embryonic stem (mES) reporter cell lines that can be used to identify the bioactivity and potential carcinogenic properties of newly developed compounds in a single test. The method uses a two-step approach.
[0291] In a first step, dose range finding was performed using wild type mES cells (line B4418). 20 different concentrations of each compound were tested, starting with 10 mM in DMSO as the highest concentration, and 19 serial 2-fold dilutions.
[0292] Next, genotoxicity was assessed using specific genes linked to reporter genes for detecting DNA damage; the specific genes were Bscl2 (as explained by US9695481B2 and EP2616484B1) and Rtkn (Hendriks et al., Toxicol. Sci. 2015, 150, 190-203) biomarkers. Genotoxicity was assessed at 10%, 25% and 50% cytotoxicity in the absence and presence of a metabolic system based on rat S9 liver extract (aroclor1254-induced rats, Moltox, Boone, NC, USA). Independent cell lines were inoculated into 96-well cell culture plates, and fresh ES cell culture medium containing diluted test substances was added to the cells 24 hours after the cells were inoculated into the 96-well plates. For each compound tested, five concentrations were tested at 2-fold dilutions. The highest sample concentration will induce significant cytotoxicity (50-70%). In case of no or low cytotoxicity, 10 mM or the maximum soluble mixture concentration was used as the maximum tested concentration.Cytotoxicity was determined by cell counting after 24 hours of exposure using a Guava easyCyte 10HT flow cytometer (Millipore).
[0293] GFP reporter gene induction is always compared with vehicle control treatment. For specific compounds, the DMSO concentration in all wells is similar and never exceeds 1%. All compounds were tested in at least three completely independent repeated experiments. All experiments included positive control treatment (DNA damage) using cisplatin. Metabolism was assessed by adding S9 liver extract. In the presence of S9 and required cofactors (RegenSysA+B, Moltox, Boone, NC, USA), cells were exposed to five concentrations of test compounds for 3 hours. After washing, cells were incubated in fresh ES cell culture medium for 24 hours. After exposure for 24 hours, the induction of GFP reporter gene was determined using Guava easyCyte 10HT flow cytometer (Millipore). Only GFP expression in complete single cells was determined. The average GFP fluorescence and cell concentration in each well were measured, and the average GFP fluorescence and cell concentration were used for cytotoxicity assessment. ToxPlot software (Toxys, Leiden, the Netherlands) was used to analyze data. Induction levels reported are at compound concentrations that induce 10%, 25% and 50% cytotoxicity after 3 hours of exposure in the presence of S9 rat liver extract and 24 hours of recovery or alternatively after 24 hours of exposure in the absence of S9 rat liver extract.
[0294] A positive induction level of a biomarker is defined as equal to or higher than a 2-fold induction at at least one of 10%, 25% and 50% cytotoxicity in the absence or presence of a metabolic system rat S9 liver extract; a weak positive induction is defined as higher than 1.5-fold and lower than 2-fold induction at at least one of 10%, 25% and 50% cytotoxicity in the absence or presence of a metabolic system rat S9 liver extract (but lower than 2-fold at 10%, 25% and 50% cytotoxicity), and a negative induction is defined as lower than or equal to a 1.5-fold induction at 10%, 25% and 50% cytotoxicity in the absence or presence of a metabolic system based on rat S9 liver extract.
[0295] Components and abbreviations used:
[0296] 2-Methylaziridine (propylene imine, CAS No. 75-55-8) was obtained from Menadiona SL (Palafolls, Spain).
[0297] n-Butyl glycidyl ether (CAS No. 2426-08-6) was obtained from Alfa Aesar (a subsidiary of Thermo Fisher Scientific).
[0298] Potassium carbonate (CAS No. 584-08-7) was obtained from Alfa Aesar (a subsidiary of Thermo Fisher Scientific).
[0299] Bismuth neodecanoate (CAS No. 34364-26-6) was obtained from TIB chemicals AG (Mannheim, Germany).
[0300] 2-Methyltetrahydrofuran (CAS No. 96-47-9) was obtained from Merck KgaA.
[0301] N3600, N3800, N3900 and XP2860 was obtained from Covestro.
[0302] Acetone (CAS No. 67-64-1) was obtained from Sigma-Aldrich.
[0303] Triethylamine (TEA, CAS No. 121-44-8) was obtained from Arkema.
[0304] Maxemul TM 7101 was obtained from Croda Int. PLC.
[0305] Trimethylolpropane tris(2-methyl-1-aziridine propionate), CAS No. 64265-57-2, CX-100 was obtained from DSM.
[0306] Atlas TM G-5000 was obtained from Croda Int. PLC.
[0307] Dimethylolpropionic acid (DMPA, CAS No. 4767-03-7) was obtained from Perstop Polyols.
[0308] pTHF650 (polytetramethylene ether glycol with an OH value of 172 mg KOH / g) was obtained from BASF.
[0309] IPDI (5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane, I, isophorone diisocyanate, CAS No. 4098-71-9) was obtained from Covestro.
[0310] Hydrazine (16% aqueous solution, CAS No. 302-01-2) was obtained from Honeywell.
[0311] Sodium lauryl sulfate (30% aqueous solution, CAS No. 73296-89-6) was obtained from BASF.
[0312] Methyl methacrylate (CAS No. 80-62-6) was obtained from Lucite Int.
[0313] n-Butyl acrylate (CAS No. 141-32-2) was obtained from Dow Chemical.
[0314] Methacrylic acid (CAS No. 79-41-4) was obtained from Lucite Int.
[0315] Ammonium persulfate (CAS No. 7727-54-0) was obtained from United Initiators.
[0316] Ammonia (25% aqueous solution, CAS No. 1336-21-6) was obtained from Merck.
[0317] Tin 2-ethylhexanoate (CAS No. 301-10-0) was obtained from Sigma-Aldrich.
[0318] D3403 was obtained from Evonik.
[0319] 3-Methyl-1-phenyl-2-phosphole-1-oxide (CAS No. 707-61-9) was obtained from Sigma-Aldrich.
[0320] 1-Methoxy-2-propyl acetate (MPA, propylene glycol methyl ether acetate, CAS No. 108-65-6) was obtained from Shell Chemicals.
[0321] 1-(2-Hydroxyethyl)ethyleneimine) (CAS No. 1072-52-2) was obtained from Tokyo Chemical Industry Co., Ltd.
[0322] DBTDL (dibutyltin dilaurate, CAS No. 77-58-7) was obtained from Reaxis.
[0323] Dimethylformamide (CAS No. 68-12-2) was obtained from Acros Organics (a subsidiary of Thermo Fisher Scientific).
[0324] T 1890 / 100, an isocyanurate based on isophorone diisocyanate (CAS No. 67873-91-0) was obtained from Evonik.
[0325] Methyl ethyl ketone (MEK, 2-butanone, CAS No. 78-93-3) was obtained from Alfa Aesar (a subsidiary of Thermo Fisher Scientific).
[0326] Atlas TM G-5002L-LQ was obtained from Croda Int. PLC.
[0327] 1-Butanol (CAS No. 71-36-3) was obtained from Sigma-Aldrich (a subsidiary of Merck KGaA).
[0328] 2-Ethylhexyl glycidyl ether (CAS No. 2461-15-6) was obtained from Sigma-Aldrich (a subsidiary of Merck KGaA).
[0329] H12MDI (4,4'-methylenebis(phenyl isocyanate, W, CAS number 101-66-8) was obtained from Covestro.
[0330] Ymer TM N-120 was obtained from Perstorp.
[0331] Potassium hydroxide (CAS No. 1310-58-3) was obtained from Sigma-Aldrich.
[0332] Cardura E10P (CAS No. 26761-45-5) was obtained from Hexion Inc.
[0333] Polypropylene glycol with an average Mn of 400Da (PPG400, Voranol TM P-400) was obtained from Dow Inc., and polypropylene glycol with an average Mn of 1000 Da (CAS No. 25322-69-4) was obtained from BASF.
[0334] Toluene (CAS No. 108-88-3) was obtained from Sigma-Aldrich.
[0335] Bisphenol A diglycidyl ether (CAS No. 1675-54-3) was obtained from Tokyo Chemical Industry Co., Ltd.
[0336] Ethyl diglycol (CAS No. 111-90-0) was obtained from Acros Organics (a subsidiary of Thermo Fisher Scientific).
[0337] Texanol TM(CAS No. 25265-77-4) was obtained from Eastman.
[0338] Butyl glycol (CAS No. 111-76-2) was obtained from Sigma-Aldrich.
[0339] Butyl diglycol (CAS No. 112-34-5) was obtained from Alfa Aesar (a subsidiary of Thermo Fisher Scientific).
[0340] Byk 347 was obtained from BYK.
[0341] Gel L 75 N was obtained from Borchers.
[0342] A-2092 was obtained from DSM.
[0343] XK-12 was obtained from DSM.
[0344] XK-190 was obtained from DSM.
[0345] R-520 was obtained from DSM.
[0346] NeoPac TM PU-480 was obtained from DSM.
[0347] R-600 was obtained from DSM.
[0348] XK-82 was obtained from DSM.
[0349] R-1888 was obtained from DSM.
[0350] XK-98 was obtained from DSM.
[0351] R-1005 was obtained from DSM.
[0352] Example 1
[0353] A 1 L round bottom flask equipped with a condenser was placed under N2 atmosphere and charged with propylene imine (120 g), n-butyl glycidyl ether (189.0 g) and K2CO3 (15.0 g) and heated to 80° C. within 30 minutes, after which the mixture was stirred for 21 h at T = 80° C. After filtration, excess PI was removed in vacuo, followed by further purification by vacuum distillation to obtain a colorless, low-viscosity liquid.
[0354] 186.2 g of the resulting material (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) was charged to a reaction flask equipped with a thermometer along with 0.02 g of bismuth neodecanoate and 77.8 g of 2-methyltetrahydrofuran. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50° C. A solution of 200 g of Desmodur N 3600 in 77.8 g of 2-methyltetrahydrofuran was then added dropwise to the reaction flask over 45 minutes, after which the mixture was further heated to 70° C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 The solvent was removed by vacuum to obtain a clear light yellow high viscosity liquid. The calculated molecular weight of the theoretical main component is 1065.74 Da, and the chemical structure is shown below.
[0355]
[0356] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1088.74 Da; observed [M+Na+] = 1088.78 Da. The following components with a mass below 580 Da were determined and quantified by LC-MS:
[0357]
[0358] present in the composition at 0.21% by weight, and
[0359]
[0360] Present at less than 0.01 wt%.
[0361] Genotoxicity testing
[0362]
[0363] The results of the genotoxicity test showed that the crosslinker composition of Example 1 was non-genotoxic.
[0364] Subsequently, 300 g of the viscous liquid obtained in the previous step was mixed with 150 g of acetone and incubated at 50°C until a homogeneous solution was obtained. To this solution was added 0.5 g of triethylamine (TEA) and then 30 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The mixer stirred the resulting mixture at 2,000 rpm for 5 minutes at room temperature. Then, the stirring was increased to 10,000 rpm, and 300 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA to obtain crosslinker dispersion 1.
[0365] Genotoxicity testing
[0366]
[0367] The results of the genotoxicity test showed that the dispersion of Example 1 was non-genotoxic.
[0368] Obtained from DSM A-2092 is a widely used poly(styrene-co-acrylate-co-methacrylate) dispersion with a hydrodynamic diameter of 106 nm and an acid value of 55.3 mgKOH / g solid. To create the coating composition, 94 g of 1% ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. To A-2092 was added 18.5 g of Crosslinker Dispersion 1. After addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0369] Based on the procedure from DIN 68861-1 standard, the functional performance and stability of the coating composition were evaluated using a spot test on the coating surface, and viscosity was measured using a Brookfield DVE-LV viscometer (using the lowest of S62, S63 or S64 spindles, as allowed by the sample at 60rpm). For these tests, the coating composition was stored in an oven at 50°C for 4 weeks. The viscosity of the coating composition was determined weekly. In addition, a sample of this coating composition was filtered weekly and applied to a Leneta test card using a 100μm wire applicator (test 1). As a reference, a film was also cast from the same (aged) composition lacking a crosslinker dispersion (test blank). The film was dried at 25°C for 1 hour and then annealed at 50°C for 16 hours. Subsequently, a piece of cotton wool was immersed in 1:1 EtOH: demineralized water and placed on the film for 1 hour. After removing EtOH and recovering for 60 minutes, the following results were obtained (score 1 indicates complete degradation of the film, 5 indicates no visible damage):
[0370] Performance and stability testing
[0371]
[0372] Example 2
[0373] The crosslinking agent was synthesized and dispersed as in Example 1.
[0374] Under continuous stirring with a propeller stirrer, 280 g of 110.2 g of crosslinker dispersion 1 was gradually added to A-2092. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 8.7.
[0375] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0376] Performance and stability testing
[0377]
[0378] Example 3
[0379] The crosslinking agent was synthesized and dispersed as in Example 1.
[0380] Obtained from DSM XK-12 is a highly resistant self-crosslinking poly(acrylate-co-methacrylate) with a hydrodynamic diameter of 111 nm and an acid value of 24.2 mgKOH / g solid. To create the coating composition, 900 g of 90 g of ethyl diglycol were added to XK-12. 45.5 g of crosslinker dispersion 1 were gradually added to 280 g of this mixture over 10 minutes with continuous stirring using a propeller stirrer. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 8.8.
[0381] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0382] Performance and stability testing
[0383]
[0384] Example 4
[0385] The crosslinking agent was synthesized and dispersed as in Example 1.
[0386] Obtained from DSM XK-190 is an anti-blocking poly(acrylate-co-methacrylate) with a hydrodynamic diameter of 115 nm and an acid value of 38.9 mgKOH / g solid. To create the coating composition, 900 g of Add 9g of Texanol to XK-190 TM To 280 g of this mixture, 71.2 g of crosslinker dispersion 1 were gradually added over 10 minutes under continuous stirring with a propeller stirrer. After the addition, the coating composition was stirred for a further 5 minutes, filtered and stored. The pH of the coating composition was measured to be 9.1.
[0387] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0388] Performance and stability testing
[0389]
[0390] Example 5
[0391] The crosslinking agent was synthesized and dispersed as in Example 1.
[0392] Obtained from DSM R-520 is a UV curable poly(urethane-co-acrylate) with a hydrodynamic diameter of 79 nm and an acid value of 25.7 mgKOH / g solids. To create the coating composition, 900 grams of NeoRad TM R-520 was added with 27 grams of butyl glycol. To 280 grams of this mixture, 40.0 grams of crosslinker dispersion 1 were gradually added over 10 minutes under continuous stirring with a propeller stirrer. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 8.2.
[0393] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0394] Performance and stability testing
[0395]
[0396] Example 6
[0397] The crosslinking agent was synthesized and dispersed as in Example 1.
[0398] NeoPac from DSM TMPU-480 is a fast-drying polyurethane-alkyd hybrid with a hydrodynamic diameter of 107 nm and an acid value of 18.5 mgKOH / g solid. To create the coating composition, 900 g of NeoPac TM 32.9 g of crosslinker dispersion 1 was gradually added to PU-480. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 9.0.
[0399] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0400] Performance and stability testing
[0401]
[0402] Example 7
[0403] The crosslinking agent was synthesized and dispersed as in Example 1.
[0404] R-600 was obtained from DSM and is a polyurethane with excellent adhesion, a hydrodynamic diameter of 49 nm and an acid value of 21.3 mg KOH / g. To create the coating composition, 900 g of R-600 was added with 19 grams of ethyl diglycol. To 280 grams of this mixture, 30.1 grams of crosslinker dispersion 1 were gradually added over 10 minutes under continuous stirring with a propeller stirrer. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 8.5.
[0405] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0406] Performance and stability testing
[0407]
[0408] Example 8
[0409] The crosslinking agent was synthesized and dispersed as in Example 1.
[0410] Obtained from DSM XK-82 is a highly water-resistant poly(styrene-co-acrylate-co-methacrylate) having a hydrodynamic diameter of 134 nm and an acid value of 50.5 mg KOH / g solid. To create the coating composition, 807 g of 40.4 g of ethyl diglycol and 40.4 g of butyl glycol were added to XK-82. 75.8 g of crosslinker dispersion 1 were gradually added to 250 g of this mixture over 10 minutes with continuous stirring using a propeller stirrer. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 9.1.
[0411] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0412] Performance and stability testing
[0413]
[0414] Example 9
[0415] The crosslinking agent was synthesized and dispersed as in Example 1.
[0416] Obtained from DSM R-1888 is a hail-resistant polyurethane with a hydrodynamic diameter of 102 nm and an acid value of 22.8 mg KOH / g solid. To create the coating composition, 280 g of 38.9 grams of crosslinker dispersion 1 were added to R-1888. After addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 8.1.
[0417] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0418] Performance and stability testing
[0419]
[0420] Example 10
[0421] The crosslinking agent was synthesized and dispersed as in Example 1.
[0422] Obtained from DSM XK-98 is a fast-drying self-crosslinking poly(acrylate-co-methacrylate) having a hydrodynamic diameter of 59 nm and an acid value of 18.0 mg KOH / g solid. To create the coating composition, 900 g of 28 grams of butyl diglycol were added to XK-98. 40.5 grams of crosslinker dispersion 1 were gradually added to 280 grams of this mixture over 10 minutes under continuous stirring with a propeller stirrer. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 8.2.
[0423] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0424] Performance and stability testing
[0425]
[0426] Embodiment 11
[0427] The crosslinking agent was synthesized and dispersed as in Example 1.
[0428] To create the coating composition, 65 g of 2.0 g of butyl diglycol were added to XK-98, followed by gradual addition of 5.5 g of crosslinker dispersion 1 over 10 minutes with continuous stirring with a propeller stirrer. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0429] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0430] Performance and stability testing
[0431]
[0432] Example 12
[0433] The crosslinking agent was synthesized as in Example 1.
[0434] Subsequently, 30 g of the viscous liquid obtained in the previous step was mixed with 15 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 3.0 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 30 grams of demineralized water adjusted to pH 9 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred for another 10 minutes at 5,000 rpm, and the pH of the dispersion was set to 9 with TEA.
[0435] Obtained from DSM R-1005 is a flexible polyurethane with a hydrodynamic diameter of 62 nm and an acid value of 15.9 mg KOH / g solid. The coating composition was created by adding 15 g of the crosslinker dispersion obtained in the previous step dropwise to 158 g of TEA set to pH = 9 under continuous stirring with a propeller stirrer. R-1005. After addition, the coating composition was stirred for an additional 5 minutes, filtered and stored.
[0436] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0437] Performance and stability testing
[0438]
[0439] Embodiment 13
[0440] The crosslinking agent was synthesized as in Example 1.
[0441] Subsequently, 30 g of the viscous liquid obtained in the previous step was mixed with 15 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 3.0 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 30 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred for another 10 minutes at 5,000 rpm, and the pH of the dispersion was set to 10 with TEA.
[0442] The coating composition was created by adding 15 g of the crosslinker dispersion obtained in the previous step dropwise to 158 g of TEA set to pH = 10, under continuous stirring with a propeller stirrer. R-1005. After addition, the coating composition was stirred for an additional 5 minutes, filtered and stored.
[0443] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0444] Performance and stability testing
[0445]
[0446] * The coating composition gelled during the fourth week of storage.
[0447] Comparative Example C1
[0448] For Comparative Example C1, the crosslinker CX-100—trimethylolpropane tris(2-methyl-1-aziridine propionate) was used:
[0449]
[0450] 7.5 g of this crosslinker was mixed with 3.75 g of acetone and incubated at 50°C until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine and then 0.75 g of molten Atlas TM G-5000 dispersant. Using IKA T25 Digital with S25 N-18G head The mixer stirred the resulting mixture at 2,000 rpm for 5 minutes at room temperature. Then, the stirring was increased to 10,000 rpm, and 7.5 grams of demineralized water adjusted to pH 9 using triethylamine (TEA) was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting mixture was stirred at 5,000 rpm for another 10 minutes, and the pH of the mixture was set to 9.
[0451] The coating composition was created by adding 6 g of the crosslinker mixture obtained in the previous step dropwise to 158 g of TEA set to pH = 9, under continuous stirring with a propeller stirrer. R-1005. After addition, the coating composition was stirred for an additional 5 minutes, filtered and stored.
[0452] Based on the procedure from DIN 68861-1 standard, the functional performance and stability of the coating composition were evaluated using a spot test on the coating surface, and viscosity measurements were performed using a Brookfield DVE-LV viscometer (using the lowest of S62, S63 or S64 spindles, as allowed by the sample at 60 rpm). For these tests, the coating composition was stored in an oven at 50°C for 4 weeks. The viscosity of the coating composition was determined weekly. In addition, a sample of this coating composition was filtered weekly and applied to a Leneta test card using a 100 μm wire applicator (test C1). As a reference, a film was also cast from the same (aged) composition lacking a crosslinker dispersion (test blank). The film was dried at 25°C for 1 hour and then annealed at 50°C for 16 hours. Subsequently, a piece of cotton wool was immersed in 1:1 EtOH: demineralized water and placed on the film for 1 hour. After removing EtOH and recovering for 60 minutes, the following results were obtained (score 1 indicates complete degradation of the film, 5 indicates no visible damage):
[0453] Performance and stability testing
[0454]
[0455] * The coating composition gelled during the second week of storage.
[0456] Comparative Example C2
[0457] For Comparative Example C2, the crosslinker CX-100—trimethylolpropane tris(2-methyl-1-aziridine propionate) was used:
[0458]
[0459] 7.5 g of this crosslinker was mixed with 3.75 g of acetone and incubated at 50°C until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine and then 0.75 g of molten Atlas TM G-5000 dispersant. Using IKA T25 Digital with S25 N-18G head The mixer stirred the resulting mixture at 2,000 rpm for 5 minutes at room temperature. Then, the stirring was increased to 10,000 rpm, and 7.5 grams of demineralized water adjusted to pH 10 using triethylamine (TEA) was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting mixture was stirred for another 10 minutes at 5,000 rpm, and the pH of the mixture was set to 10.
[0460] The coating composition was created by adding 6 g of the crosslinker mixture obtained in the previous step dropwise to 158 g of TEA set to pH = 10, under continuous stirring with a propeller stirrer. R-1005. After addition, the coating composition was stirred for an additional 5 minutes, filtered and stored.
[0461] The functional properties and stability of the coating compositions were evaluated as in Comparative Example C1.
[0462] Performance and stability testing
[0463]
[0464] * The coating composition gelled during the second week of storage.
[0465] Embodiment 14
[0466] The crosslinking agent was synthesized and dispersed as in Example 1.
[0467] To create the coating composition, 250 g of To R-1005 was added 10.7 grams of the previously obtained crosslinker dispersion 1. After the addition, the coating composition was stirred for another 5 minutes, filtered and stored. The pH of the coating composition was measured to be 10.1.
[0468] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0469] Performance and stability testing
[0470]
[0471] Embodiment 15
[0472] The crosslinking agent was synthesized and dispersed as in Example 1.
[0473] The waterborne polyurethane adhesive was synthesized as follows.
[0474] DMPA (12.9 g), pTHF650 (168.4 g) and IPDI (140.5 g) were loaded into a 1L flask equipped with a thermometer and an overhead stirrer. The reaction mixture was placed under a N2 atmosphere, heated to 50°C, and 0.03 g of bismuth neodecanoate was added. The mixture was exothermic and kept at 90°C for 2.5 hours. The NCO content of the resulting urethane prepolymer was 8.00% (theoretically 8.80%) on a solid basis. The prepolymer was cooled to 75°C and TEA (8.73 g) was added, and the resulting mixture was stirred for 15 minutes. A dispersion of the resulting prepolymer was prepared by feeding 290 g of the prepolymer into demineralized water (686 g) at room temperature within 30 minutes. After the feeding was complete, the mixture was stirred for 5 minutes and hydrazine (16% aqueous solution, 51.0 g) was added. The dispersion was stirred for another 1 hour. Subsequently, the mixture was cooled to room temperature and made to 30% solid with additional demineralized water.
[0475] The waterborne polyurethane adhesive was prepared as follows. First, a 200 g amount of the adhesive was set to pH = 10 using TEA. Then, 8.4 g of butyl diglycol was added dropwise under continuous stirring with a propeller stirrer, followed by 0.25 g of Byk 347 and 0.50 g of A mixture of Gel L 75N (1 part by weight) and water (5 parts by weight) was added. After these additions, the coating composition was stirred for a further 5 minutes, filtered and stored.
[0476] The coating composition was created by adding 4.6 g of the previously obtained crosslinker dispersion 1 dropwise to 158 g of the aqueous polyurethane formulation obtained in the previous step under continuous stirring with a propeller stirrer. After the addition, the coating composition was stirred for a further 5 minutes, filtered and stored.
[0477] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0478] Performance and stability testing
[0479]
[0480] Example 16
[0481] The crosslinking agent was synthesized and dispersed as in Example 1.
[0482] A waterborne polyacrylate-co-methacrylate adhesive was synthesized as follows.
[0483] A 2L four-necked flask equipped with a thermometer and an overhead stirrer was charged with sodium dodecyl sulfate (30% solids in water, 8.38 g solution) and demineralized water (641 g). The reactor phase was placed under a N2 atmosphere and heated to 82°C. A mixture of demineralized water (101 g), sodium dodecyl sulfate (30% solids in water, 33.5 g solution), methyl methacrylate (209.8 g), n-butyl acrylate (403.2 g), and methacrylic acid (15.72 g) was placed in a large feed funnel and emulsified with an overhead stirrer (monomer feed). Ammonium persulfate (1.58 g) was dissolved in demineralized water (80.8 g) and placed in a small feed funnel (initiator feed). Ammonium persulfate (1.58 g) was dissolved in demineralized water (9.5 g) and this solution was added to the reactor phase. Immediately thereafter, 5% by volume of the monomer feed was added to the reactor phase. The reaction mixture was then allowed to exotherm to 85° C. and maintained at 85° C. for 5 minutes. The remaining monomer feed and initiator feed were then fed to the reaction mixture over 90 minutes, maintained at a temperature of 85° C. After the feeds were complete, the monomer feed funnel was rinsed with demineralized water (17.0 g) and the reaction temperature was maintained at 85° C. for 45 minutes. Subsequently, the mixture was cooled to room temperature and adjusted to pH=8.2 with ammonia solution (6.25% by weight in demineralized water) and to 40% solids with additional demineralized water.
[0484] To create the coating composition, 17.1 g of the previously obtained crosslinker dispersion 1 were gradually added to 150 g of the aqueous polyacrylate-co-methacrylate adhesive obtained as described above over a period of 10 minutes, under continuous stirring with a propeller stirrer. After the addition, the coating composition was set to pH=10 with TEA, stirred for a further 5 minutes, filtered and stored.
[0485] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0486] Performance and stability testing
[0487]
[0488] Comparative Example C3
[0489] Under nitrogen atmosphere, at 20-25 ℃, while stirring, 21.3 grams of 1-propanol were added to 78.7 grams of isophorone diisocyanate (IPDI) and 0.01 grams of 2-ethylhexanoate tin over a period of 6 hours. After standing overnight, 196.3 grams of IPDI, 74.1 grams of Tegomer D3403 and 2.4 grams of 3-methyl-1-phenyl-2-phosphocyclopentene-1-oxide were added. The mixture was heated to 150 ℃ while stirring. The mixture was maintained at 150 ℃ until the NCO content was 7.0 weight %. The mixture was cooled to 80 ℃ and 333 grams of 1-methoxy-2-propyl acetate (MPA) were added. A solution of isocyanate functional polycarbodiimide having a solid content of 50.6 weight % and an NCO content of 7.0 weight % based on solids was obtained.
[0490] To 100 grams of this isocyanate functional polycarbodiimide, 7.0 grams of 1-(2-hydroxyethyl)ethyleneimine were added. One drop of dibutyltin dilaurate was added. The mixture was heated to 80° C. while stirring. The mixture was kept at 80° C. for 1 hour. FTIR showed a small amount of residual isocyanate signal, which disappeared after a few days. The solution was further diluted with 8.0 grams of MPA to obtain a yellow solution with a solids content of 50.4% by weight. This aziridine functional carbodiimide contains 3.2 meq of acid-reactive groups (i.e., aziridine and carbodiimide functionalities) per gram of solids.
[0491] The general structure of this carbodiimide is depicted below.
[0492]
[0493] wherein a, b and c represent repeating units.
[0494] MALDI-TOF-MS confirmed the structure of this metabolite, as shown below:
[0495]
[0496] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 2043.34 Da; observed [M+Na+] = 2043.32 Da.
[0497] Genotoxicity test results:
[0498]
[0499] The results of the genotoxicity test showed that the crosslinker composition of Comparative Example C3 was genotoxic.
[0500] Subsequently, 10.5 g of the yellow solution obtained in the previous step was stirred at 500 rpm at room temperature using a three-blade propeller stirrer with a diameter of 50 mm. Then, 10.5 g of demineralized water was gradually added to the mixture over 15 minutes. After the addition was complete, the resulting dispersion was stirred at 1000 rpm for another 5 minutes.
[0501] The coating composition was created by adding 18.8 g of the crosslinker dispersion obtained in the previous step dropwise to 75 g of R-1005. After addition, the coating composition was stirred for an additional 5 minutes, filtered and stored.
[0502] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0503] Performance and stability testing
[0504]
[0505] * The coating composition gelled during the first week of storage.
[0506] Comparative Example C4
[0507] 13.6 grams of 1-(2-hydroxyethyl)ethyleneimine were charged into a reaction flask equipped with a thermometer together with 0.02 grams of bismuth neodecanoate and 147 grams of dimethylformamide. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50°C. A solution of 40.0 grams of Vestanat T1890 / 100 in 147 grams of dimethylformamide was then added dropwise to the reaction flask over 45 minutes, followed by rinsing with an additional 10.0 grams of dimethylformamide, and the mixture was then further heated to 70°C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 The solvent was removed in vacuo to obtain a whitish solid. The calculated molecular weight of the theoretical main component is 927.62 Da, and the chemical structure is shown below.
[0508]
[0509] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 950.61 Da; observed [M+Na+] = 950.50 Da.
[0510] Subsequently, 15 g of the whitish solid obtained in the previous step was mixed with 7.5 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 1.5 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The obtained mixture was stirred by a mixer at room temperature with 2,000rpm for 5 minutes. Then, stirring was increased to 10,000rpm, and 15 grams of demineralized water adjusted to pH 10 using triethylamine were gradually added to the mixture in 15 minutes. During this interpolation process, the mixer was continuously moved around the reaction vessel. After the addition was completed, the obtained dispersion was stirred for another 10 minutes at 5,000rpm, and the pH of the dispersion was set to 10 with TEA. In 4 hours after the preparation of this based on 1-(2-hydroxyethyl) ethyleneimine was completed, the obtained dispersion was coagulated. Therefore, it is impossible to prepare an aqueous coating composition with good crosslinking efficiency and a long shelf life.
[0511] Embodiment 17
[0512] 15.6 g of 1-(2-methylaziridine-1-yl)propan-2-ol (prepared according to S.Lesniak, M.Rachwalski, S.Jarzynski, E.Obijalska Tetrahedron Asymm. 2013, 24 1336-1340) was placed in a reaction flask equipped with a thermometer together with 0.02 g of bismuth neodecanoate and 81.4 g of dimethylformamide. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50°C. A solution of 34.5 g of Vestanat T1890 / 100 in 200 g of dimethylformamide was then added dropwise to the reaction flask over 45 minutes, after which the mixture was further heated to 70°C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until the peak at 2200-2300 cm -1 The solvent was removed in vacuo to obtain a whitish solid. The calculated molecular weight of the theoretical main component is 1011.71 Da, and the chemical structure is shown below.
[0513]
[0514] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1034.70 Da; observed [M+Na+] = 1034.66 Da.
[0515] Subsequently, 9.4 g of the light yellow viscous liquid obtained in the previous step was mixed with 3.4 g of acetone and 1.3 g of methyl ethyl ketone (MEK), and incubated at 50° C. until a uniform solution was obtained. 0.03 g of triethylamine (TEA) was added to the solution, followed by 1.9 g of Atlas TM G-5002L-LQ dispersant. Use IKA T25Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 9.4 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA.
[0516] To create the coating composition, 75 g of ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. 14.1 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0517] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0518] Performance and stability testing
[0519]
[0520] Embodiment 18
[0521] 24.12 g of (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate prepared as described in Example 1 was charged into a reaction flask equipped with a thermometer together with 0.02 g of bismuth neodecanoate and 4.48 g of acetone. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50° C. A solution of 34.0 g of Vestanat T1890 / 100 in 12.80 g of acetone was then added dropwise to the reaction flask over 25 minutes, after which the mixture was further reacted at 50° C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1The mixture was stirred for 2 hours until no NCO stretching change was observed. Subsequently, 0.83 grams of 1-butanol was added to the mixture, followed by further reaction to completely eliminate the above-mentioned NCO stretching peak. Finally, the solvent was removed in vacuo to obtain a light yellow high viscosity liquid. The calculated molecular weight of the theoretical main component is 1227.88 Da, and the chemical structure is shown below.
[0522]
[0523] Subsequently, 9.4 g of the pale yellow viscous liquid obtained in the previous step was mixed with 2.0 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 1.0 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 9.5 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA.
[0524] To create the coating composition, 80 g of ethanol adjusted to pH 10 with triethylamine (TEA) were gradually added over 10 minutes under continuous stirring with a propeller stirrer. 16.2 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0525] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0526] Performance and stability testing
[0527]
[0528] Embodiment 19
[0529] A 1 L round bottom flask equipped with a condenser was placed under a N2 atmosphere and charged with propylene imine (91.0 g), 2-ethylhexyl glycidyl ether (201.0 g) and K2CO3 (10.00 g) and heated to 80° C., after which the mixture was stirred for 47 hours at T = 80° C. After filtration, excess PI was removed in vacuo, followed by further purification by vacuum distillation to obtain a colorless, low-viscosity liquid.
[0530] 130 g of the resulting material was charged into a reaction flask equipped with a thermometer along with 0.02 g of bismuth neodecanoate and 668 g of dimethylformamide. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50°C. A solution of 107.4 g of Desmodur N 3600 in 668 g of dimethylformamide was then added dropwise to the reaction flask over 45 minutes, 10 g of dimethylformamide was flushed into the reaction mixture through a feed funnel, and the mixture was then further heated to 75°C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 The solvent was removed by vacuum to obtain a highly viscous colorless liquid. The calculated molecular weight of the theoretical main component is 1233.93 Da, and the chemical structure is shown below.
[0531]
[0532] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1256.93 Da; observed [M+Na+] = 1256.86 Da. The following components with a mass below 580 Da were determined and quantified by LC-MS:
[0533]
[0534] Present at 0.16 wt%.
[0535] Subsequently, 15 g of the viscous liquid obtained in the previous step was mixed with 7.5 g of acetone and incubated at 50°C until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 1.5 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 15 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred for another 10 minutes at 5,000 rpm, and the pH of the dispersion was set to 10 with TEA.
[0536] The coating composition was created by adding 17 g of the crosslinker dispersion obtained in the previous step dropwise to 158 g of TEA set to pH = 10, under continuous stirring with a propeller stirrer. R-1005. After addition, the coating composition was stirred for an additional 5 minutes, filtered and stored.
[0537] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0538] Performance and stability testing
[0539]
[0540] * The coating composition gelled during the fourth week of storage.
[0541] Embodiment 20
[0542] 73.3 g of (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) synthesized as described in Example 1 was charged into a reaction flask equipped with a thermometer together with 0.02 g of bismuth neodecanoate and 460 g of dimethylformamide. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50° C. A solution of 162.6 g of Desmodur N 3800 in 460 g of dimethylformamide was then added dropwise to the reaction flask over 45 minutes, after which the mixture was further heated to 70° C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 The solvent was removed in vacuo to obtain a clear, light yellow, high viscosity liquid.
[0543] The calculated molecular weights of the theoretical main components are 1065.74 Da (three aziridine groups) and 1589.08 (four aziridine groups), and the chemical structures are shown below.
[0544]
[0545] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1088.74 Da; observed [M+Na+] = 1088.79 Da (three aziridine groups). Calculated [M+Na+] = 1612.07 Da; observed [M+Na+] = 1612.19 Da (four aziridine groups).
[0546] The following components with masses below 580 Da were determined and quantified by LC-MS:
[0547]
[0548] present in the composition at 0.31% by weight, and
[0549]
[0550] Present at less than 0.01 wt%.
[0551] Subsequently, 11.1 g of the viscous liquid obtained in the previous step was mixed with 4.8 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 1.1 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 11.1 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred for another 10 minutes at 5,000 rpm, and the pH of the dispersion was set to 10 with TEA.
[0552] To create the coating composition, 100 g of ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. 22.0 g of the crosslinker dispersion obtained in the previous step was added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0553] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0554] Performance and stability testing
[0555]
[0556] Embodiment 21
[0557] The (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate was prepared as described in Example 1 and 9.6 grams of the intermediate was charged into a reaction flask equipped with a thermometer together with 0.02 grams of bismuth neodecanoate and 30 grams of 2-methyltetrahydrofuran. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50° C. A solution of 10 grams of Desmodur N 3900 in 30 grams of 2-methyltetrahydrofuran was then added dropwise to the reaction flask over 45 minutes, after which the mixture was further heated to 70° C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1The mixture was stirred for 2 hours until no NCO stretching change was observed. Subsequently, 0.33 grams of 1-butanol was added to the mixture, followed by further reaction to completely eliminate the above NCO stretching peak. The solvent was removed in vacuo to obtain a clear light yellow high viscosity liquid. The calculated molecular weight of the theoretical main component is 1065.74 Da, and the chemical structure is shown below.
[0558]
[0559] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1088.74 Da; observed [M+Na+] = 1088.81 Da. The following components with a mass below 580 Da were determined and quantified by LC-MS:
[0560]
[0561] present in the composition at 0.30% by weight, and
[0562]
[0563] Present at 0.02 wt%.
[0564] Genotoxicity testing
[0565]
[0566] The results of the genotoxicity test showed that the crosslinker composition of Example 21 was non-genotoxic.
[0567] Subsequently, 14.4 g of the viscous liquid obtained in the previous step was mixed with 7.2 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 1.5 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 14.4 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA.
[0568] To create the coating composition, 150 g of ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. 22.6 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0569] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0570] Performance and stability testing
[0571]
[0572] Embodiment 22
[0573] 20 grams of Desmodur XP 2860 and 0.02 grams of bismuth neodecanoate were charged into a reaction flask equipped with a thermometer. The mixture was stirred with a mechanical upper stirrer under a nitrogen atmosphere and heated to 50° C. Then 16.40 grams of the (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate prepared as described in Example 1 was added dropwise to the reaction flask over 10 minutes, after which the mixture was further heated to 70° C. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 The reaction mixture was stirred for 2 hours until no NCO stretching change was observed. Subsequently, 0.16 grams of 1-butanol was added to the mixture, and then further reacted to completely eliminate the above-mentioned NCO stretching peak. The product is a light yellow translucent high-viscosity liquid. The calculated molecular weight of the theoretical main component is 770.55Da (propyl side group), 784.57Da (butyl side group) and 798.58Da (pentyl side group), and the chemical structure is shown below.
[0574]
[0575] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 793.55 Da; observed [M+Na+] = 793.57 Da.
[0576]
[0577] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 807.57 Da; observed [M+Na+] = 807.61 Da.
[0578]
[0579] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 821.58 Da; observed [M+Na+] = 821.63 Da. The following components with a mass below 580 Da were determined and quantified by LC-MS:
[0580]
[0581] present in the composition at 0.66% by weight, and
[0582]
[0583] Present at 0.14 wt%.
[0584] Genotoxicity testing
[0585]
[0586] The results of the genotoxicity test showed that the cross-linker composition of Example 22 had only weak positive induced genotoxicity.
[0587] Subsequently, 21.5 g of the pale yellow viscous liquid obtained in the previous step was mixed with 10.7 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 3.2 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 21.4 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA.
[0588] To create the coating composition, 60 g of ethanol adjusted to pH 10 with triethylamine (TEA) were gradually added over 10 minutes under continuous stirring with a propeller stirrer. 13.8 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0589] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0590] Performance and stability testing
[0591]
[0592] Embodiment 23
[0593] A 500 mL round bottom flask equipped with a thermometer and an overhead stirrer was placed under a N2 atmosphere and charged with Desmodur W (54.67 g) and 39.03 g of the (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate prepared as described in Example 1. The resulting mixture was heated to 50°C, after which bismuth neodecanoate (0.05 g) was added. The mixture was allowed to exotherm, after which it was further heated to 70°C and stirred at 65°C for 1 hour. To the mixture was then added 41.67 g of polypropylene glycol (PPG400) having an average Mn of 400 Da, and the mixture was stirred at 80°C for another hour. The solvent was removed in vacuo to obtain a colorless solid.
[0594] Subsequently, 11.2 g of the pale yellow viscous liquid obtained in the previous step was mixed with 5.6 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 2.2 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 11.2 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA.
[0595] To create the coating composition, 60 g of ethanol adjusted to pH 10 with triethylamine (TEA) were gradually added over 10 minutes under continuous stirring with a propeller stirrer. 21.7 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0596] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0597] Performance and stability testing
[0598]
[0599] Embodiment 24
[0600] A 500 mL round bottom flask equipped with a thermometer and an overhead stirrer was placed under a N2 atmosphere and charged with the (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate (68.70 g) prepared as described in Example 1 and Desmodur W (67.38 g). The resulting mixture was heated to 50°C, after which bismuth neodecanoate (0.02 g) was added. The mixture was allowed to exotherm to 70°C, after which it was stirred at 70°C for 60 minutes. Samples were taken at regular intervals, and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 42.43 g of Ymer N120 and 21.49 g of polyTHF650 were subsequently added to the reaction mixture set at 60°C. After a reaction time of 15 minutes, 48.0 g of acetone were added. The reaction mixture was then heated to 65°C and further reacted until the above-mentioned NCO-stretching peak completely disappeared. Subsequently, the mixture was cooled to 40°C and 250 g of demineralized water were gradually added to obtain a blue dispersion. Acetone was then removed from the dispersion using a rotary evaporator, and finally the pH of the dispersion was set to 11 using a 15% aqueous potassium hydroxide solution.
[0601] To create the coating composition, 150 g of ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. 41.1 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0602] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0603] Performance and stability testing
[0604]
[0605] Embodiment 25
[0606] A 1 L round bottom flask equipped with a condenser was placed under a N2 atmosphere and charged with propylene imine (69.0 g), Cardura E10P (201.0 g) and K2CO3 (7.30 g) and heated to 80° C., after which the mixture was stirred for 24 hours at T = 80° C. After filtration, excess PI was removed in vacuo to obtain a colorless, low-viscosity liquid.
[0607] A 500 mL round bottom flask equipped with a thermometer and an overhead stirrer was placed under a N2 atmosphere and charged with Desmodur W (49.56 g) and 53.91 g of the product of the previous step. The resulting mixture was heated to 50°C, after which bismuth neodecanoate (0.02 g) was added. The mixture was exothermic, then further heated to 80°C and stirred at 80°C for 2.5 hours. 96.48 g of polypropylene glycol (PPG1000) having an average Mn of 1000 Da was then added to the mixture, and the mixture was stirred at 80°C for another hour. The solvent was removed in vacuo to obtain a colorless solid.
[0608] Subsequently, 15 g of the colorless solid obtained in the previous step was mixed with 7.5 g of acetone and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 1.5 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 15 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred for another 10 minutes at 5,000 rpm, and the pH of the dispersion was set to 10 with TEA.
[0609] To create the coating composition, 60 g of ethanol adjusted to pH 10 with triethylamine (TEA) were gradually added over 10 minutes under continuous stirring with a propeller stirrer. 34.1 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0610] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0611] Performance and stability testing
[0612]
[0613] Embodiment 26
[0614] A 2L round-bottom flask equipped with a condenser was placed under a N2 atmosphere and charged with toluene (250 g), propylene imine (325 g), bisphenol A-diglycidyl ether (387 g) and K2CO3 (10.0 g) and heated to 70° C. within 30 min, after which the mixture was stirred for 19 h at T = 70° C. After filtration, excess PI was removed in vacuo, followed by further purification by vacuum distillation to obtain a whitish solid.
[0615] A 500 mL round bottom flask equipped with a thermometer and an overhead stirrer was placed under a N2 atmosphere and charged with the bisphenol A-PI intermediate prepared as described above (24.85 g), the (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate prepared as described in Example 1 (18.65 g), Desmodur W (33.39 g) and 22.90 g of acetone. The resulting mixture was heated to 50°C, after which bismuth neodecanoate (0.02 g) was added. The mixture was allowed to exotherm to 60°C, after which it was stirred at 60°C for 120 minutes. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak of 0.1% was observed at 2200-2300 cm -1 23.02 g of Ymer N120 was then added to the reaction mixture. The reaction mixture was then heated to 65°C and further reacted until the above-mentioned NCO-stretching peak completely disappeared, and then 25.00 g of acetone was added to dilute the reaction mixture. Subsequently, the mixture was cooled to 40°C and 166 g of demineralized water was gradually added to obtain a blue dispersion. Acetone was then removed from the dispersion using a rotary evaporator, and finally the pH of the dispersion was set to 12.5 using a 15% aqueous potassium hydroxide solution.
[0616] The calculated molecular weight of the theoretical main component and its chemical structure are shown below:
[0617]
[0618] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1375.92 Da; observed [M+Na+] = 1375.91 Da.
[0619]
[0620] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 659.47 Da; observed [M+Na+] = 659.41 Da.
[0621]
[0622] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 2622.70 Da; observed [M+Na+] = 2622.59 Da.
[0623] To create the coating composition, 75 g of ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. 15.7 g of the crosslinker dispersion obtained in the previous step were added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0624] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0625] Performance and stability testing
[0626]
[0627] Embodiment 27
[0628] A 500 mL round bottom flask equipped with a thermometer and an overhead stirrer was placed under a N2 atmosphere and charged with the bisphenol A-PI intermediate prepared as described in Example 26 (17.13 g), the (1-butoxy-3-(2-methylaziridin-1-yl)propan-2-ol) intermediate prepared as described in Example 1 (28.24 g), Desmodur W (39.55 g) and 25.00 g of acetone. The resulting mixture was heated to 60°C, after which bismuth neodecanoate (0.02 g) was added. The mixture was maintained at 60°C using a water bath throughout the exothermic reaction and then stirred at 60°C for 2 hours. Samples were taken at regular intervals and the progress of the reaction was monitored using a Bruker Alpha FT-IR spectrometer until a peak at 2200-2300 cm -1 Then, 15.08 g of Voranol P-400 was added to the reaction mixture. The reaction mixture was then allowed to react further until the above-mentioned NCO-stretching peak completely disappeared. Finally, 20.00 g of acetone was added to produce a light yellow solution. The calculated molecular weight of the theoretical main component and its chemical structure are shown below:
[0629]
[0630] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 2062.40 Da; observed [M+Na+] = 2062.39 Da.
[0631]
[0632] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 1375.92 Da; observed [M+Na+] = 1375.86 Da.
[0633]
[0634] The molecular weight was confirmed by Maldi-TOF-MS: calculated [M+Na+] = 659.47 Da; observed [M+Na+] = 659.41 Da.
[0635] The following components with masses below 580 Da were determined and quantified by LC-MS:
[0636]
[0637] is present in the composition at less than 0.01% by weight, and
[0638]
[0639] Present at less than 0.01 wt%.
[0640] Genotoxicity testing
[0641]
[0642] The results of the genotoxicity test showed that the cross-linker composition of Example 27 had only weak positive induced genotoxicity.
[0643] Subsequently, 36.5 g of the yellow solution obtained in the previous step was mixed with 6.2 g of methyl ethyl ketone (MEK) and incubated at 50° C. until a homogeneous solution was obtained. To this solution was added 0.03 g of triethylamine (TEA) and then 5.4 g of molten Maxemul TM 7101 dispersant. Use IKA T25 Digital with S 25 N-18G head The resulting mixture was stirred at 2,000 rpm for 5 minutes at room temperature by the mixer. Then, the stirring was increased to 10,000 rpm, and 26.8 grams of demineralized water adjusted to pH 10 using triethylamine was gradually added to the mixture over 15 minutes. During this addition process, the mixer was continuously moved around the reaction vessel. After the addition was complete, the resulting dispersion was stirred at 5,000 rpm for another 10 minutes, and the pH of the dispersion was set to 10 with TEA.
[0644] To create the coating composition, 75 g of ethanol adjusted to pH 10 with triethylamine (TEA) was gradually added over 10 minutes under continuous stirring with a propeller stirrer. 14.0 g of the crosslinker dispersion obtained in the previous step was added to A-2092. After the addition, the coating composition was set to pH = 10 with TEA, stirred for another 5 minutes, filtered and stored.
[0645] The functional properties and stability of the coating compositions were evaluated as in Example 1.
[0646] Performance and stability testing
[0647]
Claims
1. An aqueous coating composition comprising a polyaziridine compound and a carboxylic acid functional polymer, characterized in that (i) the aqueous coating composition is an aqueous dispersion having a pH range of 8 to 14, (ii) the aqueous dispersion comprises particles X and particles Y, wherein the particles X comprise a polyaziridine compound and the particles Y comprise a carboxylic acid functional polymer, wherein the carboxylic acid functional polymer contains a carboxylic acid group and / or a carboxylate group, and (iii) the polyaziridine compound has: a) 2 to 6 of the following structural units A: in R1 is H, R2 and R4 are independently selected from H or an aliphatic hydrocarbon group containing 1 to 4 carbon atoms, R3 is an aliphatic hydrocarbon group containing 1 to 4 carbon atoms, m is an integer from 1 to 6, R' and R" are according to (1) or (2): (1) R'=H or an aliphatic hydrocarbon group containing 1 to 14 carbon atoms; and R" = an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, an alicyclic hydrocarbon group containing 5 to 12 carbon atoms, an aromatic hydrocarbon group containing 6 to 12 carbon atoms, CH2-O-(C=O)-R”', CH2-OR”” or CH2-(OCR””’HCR””’H) n - OR""", wherein R"' is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms and R"" is an aliphatic hydrocarbon group containing 1 to 14 carbon atoms or an aromatic hydrocarbon group containing 6 to 12 carbon atoms, n is 1 to 35, R""' is independently H or an aliphatic hydrocarbon group containing 1 to 14 carbon atoms, and R""" is an aliphatic hydrocarbon group containing 1 to 4 carbon atoms, (2) R' and R" together form a saturated alicyclic hydrocarbon group containing 5 to 8 carbon atoms, t is an integer from 0 to 3, R5 is H or CH3, X and Y are according to (I), (II) or (III): (I) X and Y are both N-R6; (II) X is O and Y is N-R6; (III) X is N-R6 and Y is O, wherein R6 is H or a straight or branched hydrocarbon group containing 1 to 4 carbon atoms; b) one or more linking chains, wherein each of the linking chains links two structural units A in the structural unit A, wherein the linking chain is the shortest chain of consecutive atoms linking two structural units A; and c) a molecular weight in the range of 500 Daltons to 10,000 Daltons, wherein the molecular weight is determined using MALDI-TOF mass spectrometry; as well as d) one or more linking groups, wherein each of these linking groups connects two structural units A in the structural unit A, wherein the linking group is composed of at least one functional group selected from the following: an aliphatic hydrocarbon functional group, an alicyclic hydrocarbon functional group, an aromatic hydrocarbon functional group, an isocyanurate functional group, an iminooxadiazinedione functional group, an ether functional group, an ester functional group, an amide functional group, a carbonate functional group, a carbamate functional group, a urea functional group, a biuret functional group, an allophanate functional group, a uretdione functional group and any combination thereof.
2. The aqueous coating composition according to claim 1, characterized in that R2 is H, R3 is CH3 and R4 is H.
3. The aqueous coating composition of claim 1, wherein R2 is H, R3 is CH3 and R4 is CH3.
4. The aqueous coating composition according to any one of claims 1 to 3, characterized in that X is O, Y is NH, m is 1 and t is 0.
5. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The linker chain consists of 4 to 300 atoms, and the linker chain is a collection of covalently linked atoms consisting of i) carbon atoms, ii) carbon and nitrogen atoms, or iii) carbon, oxygen, and nitrogen atoms.
6. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The polyaziridine compound contains 2 or 3 structural units A.
7. The aqueous coating composition according to any one of claims 1 to 3, characterized in that R' is H and R" = alkyl containing 1 to 4 carbon atoms, CH2-O-(C=O)-R"', CH2-OR"" or CH2-(OCH2CH2) n -OCH3, wherein R'' is an alkyl group containing 3 to 12 carbon atoms and R"" is an alkyl group containing 1 to 14 carbon atoms.
8. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The linking group consists of at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group and optionally at least one aromatic hydrocarbon functional group and optionally an isocyanurate functional group or an iminooxadiazinedione functional group.
9. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The linking group consists of at least one aliphatic hydrocarbon functional group and / or at least one alicyclic hydrocarbon functional group and an isocyanurate functional group or an iminooxadiazinedione functional group.
10. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The polyaziridine compound comprises one or more linking groups, wherein each of the linking groups links two structural units A in the structural unit A, wherein the linking group consists of (i) at least two aliphatic hydrocarbon functional groups and (ii) an isocyanurate functional group or an iminooxadiazinedione functional group, and wherein a pendant group is present on the linking group, wherein the pendant group has the following structural formula: in n' is the number of repeating units and is 1 to 50, X is O or NH, In each repeating unit, R7 and R8 are independently H or CH3, R9 is an aliphatic hydrocarbon group, and R 10 It is an aliphatic hydrocarbon group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 5 to 20 carbon atoms, or an aromatic hydrocarbon group having 6 to 20 carbon atoms.
11. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The structural unit A is according to the following structural formula D:
12. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The polyaziridine compound is obtained by reacting at least a polyisocyanate with a compound B having the following structural formula: wherein the molar ratio of compound B to polyisocyanate is 2 to 6, and wherein m, R', R", R1, R2, R3 and R4 are as defined in any one of claims 1 to 3.
13. The aqueous coating composition according to claim 12, characterized in that The polyisocyanates mentioned are polyisocyanates with aliphatic reactivity in which all isocyanate groups are bonded directly to aliphatic or cycloaliphatic hydrocarbon groups, irrespective of whether aromatic hydrocarbon groups are also present.
14. The aqueous coating composition according to claim 11, characterized in that The number of consecutive C atoms and optionally O atoms between the N atom of the urethane group in the structural unit D and the next N atom which is present in the linking chain or is the N atom of the urethane group of another structural unit D is at most 9.
15. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The molecular weight of the polyaziridine compound is 600 Dalton to 5000 Dalton.
16. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The aqueous coating composition comprises an aziridine functional molecule having a molecular weight less than 580 Daltons in an amount less than 0.5 wt % based on the total weight of the aqueous coating composition, wherein the molecular weight is determined using LC-MS.
17. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The pH of the aqueous coating composition is in the range of 9.5 to 11.
5.
18. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The amount of water in the aqueous coating composition is at least 15 wt % and at most 90 wt % based on the total weight of the aqueous dispersion.
19. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The amount of the polyaziridine compound in the aqueous coating composition is at least 0.5 wt % and at most 50 wt % based on the total solid content of the aqueous coating composition.
20. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The amount of aziridinyl groups and the amount of carboxylic acid groups and carboxylate groups are selected so that the stoichiometric amount of aziridinyl groups on the carboxylic acid groups and carboxylate groups is from 0.1 to 2.
0.
21. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The solids content of the aqueous coating composition is at least 5 wt % and at most 55 wt %.
22. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The particles X comprising the polyaziridine compound have an average hydrodynamic diameter based on scattered intensity of 30 to 500 nanometers, measured using a method derived from the ISO 22412:2017 standard.
23. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The particles Y comprising the carboxylic acid functional polymer have an average hydrodynamic diameter based on scattered intensity of 30 to 30,000 nanometers, measured using a method derived from the ISO 22412:2017 standard.
24. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The carboxylic acid functional polymer is selected from the group consisting of vinyl polymers, polyacrylates, polymethacrylates, poly(acrylate-co-methacrylates), and mixtures thereof.
25. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The carboxylic acid functional polymer is selected from the group consisting of polyurethanes, poly(urethane-co-acrylates), poly(urethane-co-methacrylates), poly(urethane-co-acrylates-co-methacrylates), polyureas, and mixtures thereof.
26. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The carboxylic acid functional polymer has an acid number of 2 mg KOH / gram of carboxylic acid functional polymer to 135 mg KOH / gram of carboxylic acid functional polymer.
27. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The aqueous coating composition includes a dispersant.
28. The aqueous coating composition according to any one of claims 1 to 3, characterized in that The aqueous coating composition comprises a single surface-active molecular component as a dispersant, and the amount of the single surface-active molecular component is in the range of 0.1 wt % to 20 wt % based on the total weight of the aqueous coating composition.
29. The aqueous coating composition according to claim 28, characterized in that The dispersant is a polymer having a number average molecular weight of at least 2,000 Daltons and at most 1,000,000 Daltons, and the polymer is a polyether, wherein the number average molecular weight is determined using MALDI-ToF mass spectrometry.
30. The aqueous coating composition of any one of claims 1 to 3, wherein the particle X comprises neither a carboxylic acid functional polymer nor other compounds that can crosslink with the polyaziridine compound, and the particle Y comprises no polyaziridine compound.
31. according to the aqueous coating composition described in any one of claims 1-3, wherein said particle X comprises neither carboxylic acid functional polymer nor other compounds that can be crosslinked with said polyaziridine compound, and particle Y comprises neither said polyaziridine compound nor other compounds that can be crosslinked with the carboxylic acid functional group of said carboxylic acid functional polymer.
Citation Information
Patent Citations
Process for preparing cyclic amines
EP0227461B1
Screening method
EP2616484B1
Process for treatment of proteinaceous materials
US3523750A
Surface coating and method for applying same
US5133997A
Coating composition of aziridinyl polymer and epoxy polymer(s)
US5241001A